A heat color-changing tipping paper for cigarettes and a preparation method thereof
Patent Information
- Application Number
- CN202611206426.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-16
AI Technical Summary
传统烟用接装纸整体不透明,消费者仅能通过烟丝燃烧长度判断燃烧进度,无法直观观测滤嘴内部结构、受热分布及烟气浸润范围
[0016] Beneficial effects: Compared with the prior art, the present invention provides a thermochromic tipping paper for cigarettes and its preparation method, which relates to the field of cigarette packaging material technology. The thermochromic tipping paper for cigarettes includes a central transparent thermochromic zone and opaque zones located on both sides of the transparent thermochromic zone.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of cigarette packaging materials technology, and in particular to a tipping paper for temperature-sensitive color-changing cigarettes and its preparation method. Background Technology
[0002] Cigarette tipping paper is a packaging material that connects the tobacco section of a cigarette to the filter section. Traditional cigarette tipping paper is opaque, and consumers can only judge the burning progress by the length of the burning tobacco, without being able to directly observe the internal structure of the filter, the heat distribution, and the range of smoke penetration.
[0003] To achieve filter visibility, existing transparent cigarette tipping papers are mostly made using a paper-based composite plastic film process. This involves laminating a transparent film onto a paper base to achieve light transmission. However, this method suffers from drawbacks such as the plastic film's difficulty in natural degradation, its susceptibility to delamination and peeling under heat, and the difficulty in recycling, making it difficult to meet increasingly stringent environmental standards for tobacco additives. Other technologies achieve turbidity or thermochromic effects through surface coatings or printing, but the functional components lack chemical bonding or physical anchoring with the paper base, making them prone to migration and detachment during storage and use, leading to a decline or even failure of the thermochromic function. More importantly, the chemicals introduced by coatings and printing may be released in high-temperature flue gas environments, raising safety concerns that may not meet relevant standards for tobacco additives.
[0004] Therefore, there is an urgent need for a cigarette tipping paper with a paper base made entirely of plant fibers, free of petrochemical plastic film, with zoned transparency, reversible color change in dual temperature zones, and fully biodegradable.
[0005] Therefore, existing technologies still need to be improved and enhanced. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a thermochromic cigarette tipping paper that is all plant-based, zonedly transparent, and has dual-temperature zone reversible color change.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: This application provides a thermochromic cigarette tipping paper, which includes a central transparent thermochromic zone and opaque zones located on both sides of the transparent thermochromic zone; The transparent thermochromic zone comprises the following components in parts by weight: 70-80 parts of fully bleached softwood pulp, 20-30 parts of carboxylated cellulose nanofibers, 1.5-2.5 parts of cationic transparent starch, 0.3-0.8 parts of sodium carboxymethyl cellulose, 0.6-1.0 parts of food-grade sorbitol, 0.3-0.8 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.2-0.4 parts of food-grade waterborne acrylic resin, 0.8-1.5 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid; The opaque region comprises the following components in parts by weight: 80-95 parts of fully bleached hardwood pulp, 5-20 parts of fully bleached softwood pulp, 15-25 parts of heavy calcium carbonate, 1.0-2.0 parts of cationic starch, 0.1-0.3 parts of alkyl ketene dimer sizing agent, 0.8-1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid.
[0008] In some embodiments, the transparent thermochromic zone comprises the following components in parts by weight: 75 parts of fully bleached softwood pulp, 25 parts of carboxylated cellulose nanofibers, 2.0 parts of cationic transparent starch, 0.5 parts of sodium carboxymethyl cellulose, 0.8 parts of sorbitol, 0.5 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.3 parts of food-grade waterborne acrylic resin, 1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.1 parts of amphoteric polyacrylamide retention aid.
[0009] In some embodiments, the opaque region comprises the following components in parts by weight: 90 parts of fully bleached hardwood pulp, 10 parts of fully bleached softwood pulp, 20 parts of heavy calcium carbonate, 1.5 parts of cationic starch, 0.2 parts of alkyl ketene dimer sizing agent, 1.0 part of polyamide epichlorohydrin wet strength agent, and 0.1 parts of amphoteric polyacrylamide retention aid; wherein the particle size D50 of the heavy calcium carbonate is ≤0.8 μm.
[0010] In some embodiments, the internal core material of the dual-temperature zone reversible thermochromic microcapsule powder includes a leuco dye, a bisphenol S color developer, and a long-chain phase change solvent; the outer wall of the dual-temperature zone reversible thermochromic microcapsule powder is coated with melamine-formaldehyde resin; and the particle size of the dual-temperature zone reversible thermochromic microcapsule powder is 2–7 μm. The food-grade waterborne acrylic resin has a solid content of 40% to 46%, a viscosity of 800 to 1500 mPa·s at 25°C, and a glass transition temperature (Tg) of 10 to 25°C.
[0011] This application also provides a method for preparing the aforementioned thermochromic cigarette tipping paper, comprising the following steps: Prepare transparent thermochromic slurry and opaque slurry separately; Transparent thermochromic pulp and opaque pulp are simultaneously fed into the web through a partitioned dual-channel headbox and arranged alternately in fixed width units. After being dewatered by gradient negative pressure, the fibers of the two zones naturally interweave to form an integrated wet paper blank. The wet paper blank is dehydrated by ambient temperature boot press; A three-stage gradient drying process with progressively decreasing temperature is used to control the moisture content of the paper. The transparent thermochromic areas of the paper are soft-calendered, while the opaque areas are left uncalendered. The paper is then slit and rewound under low tension to obtain the finished product.
[0012] In some embodiments, the step of preparing the transparent thermochromic slurry includes: Fully bleached softwood pulp was diluted in deionized water to a disintegration concentration of 3.5%–4.0%. The fibers were then broken down in a pulper until completely dispersed without fiber bundles. Carboxylated cellulose nanofibers were then added and mixed evenly to obtain a transparent thermochromic mixed pulp. The transparent thermochromic mixed pulp was then placed in a high-consistency refiner and refined at an input concentration of 3.8%–4.2%. The pulp freeness was controlled at 92±3°SR and the average fiber length was 0.8–1.0 mm to obtain a transparent thermochromic fiber-based pulp. Under stirring conditions of 800-1000 rpm, cationic transparent starch, sodium carboxymethyl cellulose, food-grade sorbitol, polyamide epichlorohydrin wet strength agent, and amphoteric polyacrylamide retention aid are added sequentially to the transparent thermochromic fiber-based slurry. After each component is added, it is stirred and matured separately to ensure that the additives are fully dispersed and adsorbed, thus forming a transparent slurry modified with additives. The dual-temperature zone reversible thermochromic microcapsule powder and food-grade waterborne acrylic resin were premixed and dispersed evenly at room temperature. After the aforementioned additives were matured in stages, the stirring speed was reduced from 800-1000 rpm to 500 rpm under low shear stirring. Then, the dual-temperature zone reversible thermochromic microcapsule powder and food-grade waterborne acrylic resin functional materials were slowly added into the transparent slurry modified by the additives. After functional modification, the transparent slurry is diluted with deionized water to a concentration of 0.9% for online application. After stirring evenly, it is sealed and allowed to stand for 20-30 minutes to mature.
[0013] In some embodiments, the step of preparing the opaque slurry includes: Fully bleached hardwood pulp and fully bleached softwood pulp were mixed and adjusted to a disintegration concentration of 4.0% in deionized water. The pulp was then disintegrated in a pulper until completely dispersed to obtain an opaque mixed pulp. The opaque mixed pulp was then beating with a double-disc refiner to control the beating degree of the pulp at 40±3°SR, thus obtaining an opaque fiber-based pulp. At a stirring speed of 800-1000 rpm, heavy calcium carbonate, cationic starch, alkyl ketone dimer sizing agent, polyamide epichlorohydrin wet strength agent, and amphoteric polyacrylamide retention aid are added sequentially to the opaque fiber-based slurry. After each component is added, it is stirred and matured separately to ensure that the additives are fully dispersed and adsorbed, thus forming an opaque slurry modified with additives. The modified opaque slurry was diluted with deionized water to a concentration of 1.2% for online application. After stirring evenly, it was sealed and allowed to stand for 20-30 minutes to mature. In some embodiments, the transparent thermochromic zone pulp and the opaque zone pulp are simultaneously fed into the web through a partitioned dual-channel headbox, alternately arranged in fixed-width units, and dewatered under gradient negative pressure. The fibers of the two zones naturally interweave to form an integrated wet paper blank. The headbox distributes the slurry horizontally across the entire width, with each 32mm section forming an independent molding unit. Each molding unit contains a dual-channel structure: an 8mm wide transparent thermochromic slurry channel and a 24mm wide opaque slurry channel. The transparent thermochromic slurry channel is designated as Channel A, and the opaque slurry channel as Channel B. The two channels are evenly distributed horizontally in an alternating A / B pattern. A thin-walled flow-stabilizing weir is installed between each slurry channel, with a 0.3mm fiber weaving gap at the bottom. This prevents lateral flow of slurries with different filtration rates while allowing a small amount of fiber to interweave across the two zones, achieving integrated integration. The transparent thermochromic slurry channel and the opaque slurry channel are each equipped with an independent pressure-stabilizing buffer chamber, allowing for differentiated control of the two slurry flow rates to match the differences in filtration rates between the two types of slurries. During the wet paper blank forming process, the pulp supply pressure is maintained at 0.12-0.15MPa. A single pressure-stabilized pulp supply system is used for the entire width. The paper machine speed is constant at 50m / min. The uniform opening of the headbox lip is 1.1-1.3mm. The dual-channel lips within the unit are proportionally distributed. By using a vacuum chamber with progressively lower negative pressures of -10kPa, -20kPa, and -30kPa, the pulp fibers in the two zones interweave and are integrated into a single unit, resulting in an integrated wet paper blank with a dryness of 32% ± 1%.
[0014] In some embodiments, the process of dewatering the wet paper blank using a ambient temperature boot press and controlling the paper moisture content using a three-stage gradient drying process with progressively decreasing temperature includes: The formed wet paper blank is pressed at room temperature using a shoe press. The pressing environment temperature is 22-28℃, the pressing line pressure is 200kN / m, and the effective pressing zone width is 250mm. A three-stage, progressively cooling, gradient drying process is used to dehydrate the pressed paper: the first stage is a shaping drying at 100℃, with a paper throughput of 8–10 seconds; the second stage is a uniform dehydration drying at 90℃, with a paper throughput of 12–15 seconds; and the third stage is a moisture balance drying at 80℃, with a paper throughput of 10–12 seconds. The finished product moisture content is controlled at 6.0 ± 0.5%.
[0015] In some embodiments, the process of soft calendering of the transparent thermochromic areas of the paper sheet and calendering-free treatment of the opaque areas, followed by low-tension slitting and rewinding to obtain the finished product, includes: The operation of the calendering roller is controlled by a servo partitioned hydraulic pressure control structure. The 8mm transparent temperature change zone in each forming unit is softly calendered. The linear pressure of the calendering roller is 70N / mm and the roller body temperature is 45℃. The 24mm opaque zone is exempt from calendering treatment. After calendering, the paper is treated with transverse segmented hot air leveling and stretching rollers to eliminate the transverse stress difference in the paper web caused by the differentiated calendering of different zones, and to avoid uneven transverse thickness and warping of the finished product. The paper is slit and rewound with low tension of 8-12N, and the waste edges on both sides of the paper are removed to finally produce a finished cigarette tipping paper with zoned transparency and temperature-sensitive turbidity.
[0016] Beneficial effects: Compared with the prior art, the present invention provides a thermochromic tipping paper for cigarettes and its preparation method, which relates to the field of cigarette packaging material technology. The thermochromic tipping paper for cigarettes includes a central transparent thermochromic zone and opaque zones located on both sides of the transparent thermochromic zone. The transparent thermochromic zone comprises the following components in parts by weight: 70-80 parts of fully bleached softwood pulp, 20-30 parts of carboxylated cellulose nanofibers, 1.5-2.5 parts of cationic transparent starch, 0.3-0.8 parts of sodium carboxymethyl cellulose, 0.6-1.0 parts of food-grade sorbitol, 0.3-0.8 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.2-0.4 parts of food-grade waterborne acrylic resin, 0.8-1.5 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid; The opaque region comprises the following components in parts by weight: 80-95 parts of fully bleached hardwood pulp, 5-20 parts of fully bleached softwood pulp, 15-25 parts of heavy calcium carbonate, 1.0-2.0 parts of cationic starch, 0.1-0.3 parts of alkyl ketene dimer sizing agent, 0.8-1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid.
[0017] In this application, the cigarette tipping paper includes a central transparent thermochromic zone and two opaque zones on both sides. At room temperature, consumers can directly view the internal capsules and filter material distribution structure of the filter rod through the central transparent thermochromic zone. During inhalation, the filter tip gradually heats up as smoke enters, triggering the microcapsules in the transparent thermochromic zone to change color, clearly showing the heated area of the filter tip and the range of smoke action, providing clear feedback on the inhalation status. After cooling down, the thermochromic zone quickly returns to its original transparent state, achieving a reversible color-changing effect, enriching the product's visual identification and inhalation status warning functions. At the same time, the two opaque zones on both sides maintain the excellent printability and overall structural support function of traditional cigarette tipping paper, without reducing the strength and stability of the finished packaging due to the transparent thermochromic zone. The cigarette tipping paper of this application uses food-grade additives and all-plant fiber substrate, without adding petrochemical plastic films such as polyethylene and polypropylene, or harmful additives. It has no adhesive composite structure, relying on the interweaving of fibers to form a single piece, with clear and regular partition boundaries, no seams or delamination, and is biodegradable, fully complying with the food contact safety regulations for tobacco auxiliary materials and the industry's green and environmentally friendly requirements. Detailed Implementation
[0018] To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0019] Unless the context otherwise requires, throughout the specification and claims, the term "comprising" is interpreted as open-ended and encompassing, meaning "including, but not limited to." In the description of the specification, terms such as "one embodiment," "some embodiments," "exemplary embodiment," "example," or "some examples" are intended to indicate that a particular feature, structure, material, or characteristic associated with that embodiment or example is included in at least one embodiment or example of this disclosure. The illustrative representations of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics mentioned may be included in any suitable manner in any one or more embodiments or examples.
[0020] It should be noted that when a component is referred to as being "mounted on," "fixed to," or "set on" another component, it can be directly on the other component or may have an intervening component present. When a component is referred to as being "connected to" another component, it can be directly connected to the other component or may have an intervening component present.
[0021] It should also be noted that the directional terms such as left, right, up, and down in the embodiments of the present invention are only relative concepts or are based on the normal use state of the product, and should not be considered as restrictive.
[0022] Cigarette tipping paper is a packaging material that connects the tobacco section of a cigarette to the filter section. Traditional cigarette tipping paper is opaque, and consumers can only judge the burning progress by the length of the burning tobacco, without being able to directly observe the internal structure of the filter, the heat distribution, and the range of smoke penetration.
[0023] To achieve filter visibility, existing transparent cigarette tipping papers are mostly made using a paper-based composite plastic film process. This involves laminating a transparent film onto a paper base to achieve light transmission. However, this method suffers from drawbacks such as the plastic film's difficulty in natural degradation, its susceptibility to delamination and peeling under heat, and the difficulty in recycling, making it difficult to meet increasingly stringent environmental standards for tobacco additives. Other technologies achieve turbidity or thermochromic effects through surface coatings or printing, but the functional components lack chemical bonding or physical anchoring with the paper base, making them prone to migration and detachment during storage and use, leading to a decline or even failure of the thermochromic function. More importantly, the chemicals introduced by coatings and printing may be released in high-temperature flue gas environments, raising safety concerns that may not meet relevant standards for tobacco additives.
[0024] Therefore, there is an urgent need for a cigarette tipping paper with a paper base made entirely of plant fibers, free of petrochemical plastic film, with zoned transparency, reversible color change in dual temperature zones, and fully biodegradable.
[0025] This invention discloses a thermochromic cigarette tipping paper, which includes a central transparent thermochromic zone and opaque zones located on both sides of the transparent thermochromic zone. The transparent thermochromic zone comprises the following components in parts by weight: 70-80 parts of fully bleached softwood pulp, 20-30 parts of carboxylated cellulose nanofibers, 1.5-2.5 parts of cationic transparent starch, 0.3-0.8 parts of sodium carboxymethyl cellulose, 0.6-1.0 parts of food-grade sorbitol, 0.3-0.8 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.2-0.4 parts of food-grade waterborne acrylic resin, 0.8-1.5 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid; The opaque region comprises the following components in parts by weight: 80-95 parts of fully bleached hardwood pulp, 5-20 parts of fully bleached softwood pulp, 15-25 parts of heavy calcium carbonate, 1.0-2.0 parts of cationic starch, 0.1-0.3 parts of alkyl ketene dimer sizing agent, 0.8-1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid.
[0026] In this embodiment, the cigarette tipping paper includes a central transparent thermochromic zone and two opaque zones on both sides. The finished cigarette tipping paper has a total width of 32mm, with the central transparent thermochromic zone being 8mm wide and two 12mm wide opaque zones on either side. At room temperature, consumers can directly see the internal capsules and filter material distribution structure of the filter rod through the central transparent thermochromic zone. When inhaling, the filter tip gradually heats up as smoke enters, and the transparent thermochromic zone is heated, triggering the microcapsules to change color, which can intuitively show the heated area of the filter tip and the range of smoke action, clearly providing feedback on the inhalation status. After cooling down, the thermochromic zone can quickly return to its original transparent state, achieving a reversible cyclic color-changing effect, enriching the product's visual recognition and inhalation status warning functions. At the same time, the two opaque zones on both sides maintain the excellent printability and overall structural support function of traditional cigarette tipping paper, and the setting of the transparent thermochromic zone does not reduce the strength of the finished packaging or its stability in use.
[0027] It should be noted that the total weight of the fully bleached softwood pulp and carboxylated cellulose nanofibers is 100 parts; the overall thickness of the finished cigarette tipping paper in this application is 75±5μm, while the thickness of similar functional tipping papers in the industry is 60~95μm; the embodiment of this application takes a cigarette tipping paper with a total width of 32mm, a transparent temperature-changing zone of 8mm in the middle, and 12mm wide opaque zones on both sides of the transparent temperature-changing zone as an example to describe the formulation components, weight parts and preparation process.
[0028] In this application, the transparent thermochromic zone utilizes a highly transparent paper-based structure constructed from a blend of fully bleached softwood pulp and carboxylated cellulose nanofibers. This structure exhibits high light transmittance at room temperature, allowing clear observation of the filter's internal structure without obstruction of view. It is further enhanced by cationic transparent starch and sodium carboxymethyl cellulose to synergistically fill the fiber gaps. Combined with food-grade sorbitol for plasticizing and water retention, and food-grade water-based acrylic resin for anchoring the dual-temperature zone reversible thermochromic microcapsule powder, this effectively prevents the thermochromic material from detaching or breaking, ensuring stable thermochromic performance. Both the transparent and opaque zones employ specialized formulation systems tailored to specific functional requirements. The opaque zone utilizes a hardwood pulp-based fiber system combined with heavy calcium carbonate to achieve efficient light-blocking, while an alkyl ketene dimer sizing agent imparts excellent water resistance to the finished product. Both zones contain polyamide epichlorohydrin wet strength agent and amphoteric polyacrylamide retention aid, which can effectively improve the retention rate of fibers, fillers and functional microcapsules, strengthen the fiber cross-linking structure, and give the finished product excellent resistance to saliva and moisture. It is less prone to softening, delamination and paper damage during the rolling process, and the paper interruption rate is low in high-speed cigarette production.
[0029] This product uses food-grade additives and a fully plant-based fiber substrate, without the addition of petrochemical plastic films such as polyethylene and polypropylene, or harmful additives. It features a non-adhesive composite structure, relying on the interweaving of fibers to form a single, seamless, and non-delaminating structure. It is biodegradable and fully complies with tobacco additive food contact safety regulations and industry green environmental protection requirements. Simultaneously, cationic transparent starch and cationic starch effectively enhance the fiber bonding strength between the two zones, while sorbitol improves the brittleness of the transparent paper film, effectively preventing warping and cracking in the finished product. Heavy calcium carbonate in the opaque zone optimizes the paper surface smoothness, resulting in excellent compatibility for printing, hot stamping, and rolling processes. Furthermore, the dual-temperature zone reversible thermochromic microcapsule powder is encapsulated and anchored with food-grade water-based acrylic resin, effectively preventing dye migration and leakage from the core material. Even after long-term storage and repeated temperature cycles, the light transmittance and reversible color-changing effect show no significant attenuation. It exhibits sensitive temperature response, excellent long-term stability, and its core indicators such as wet strength and air permeability are suitable for the requirements of high-speed cigarette rolling production.
[0030] In a preferred embodiment of this application, the transparent thermochromic zone comprises the following components in parts by weight: 75 parts of fully bleached softwood pulp, 25 parts of carboxylated cellulose nanofibers, 2.0 parts of cationic transparent starch, 0.5 parts of sodium carboxymethyl cellulose, 0.8 parts of sorbitol, 0.5 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.3 parts of food-grade waterborne acrylic resin, 1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.1 parts of amphoteric polyacrylamide retention aid.
[0031] Specifically, fully bleached softwood pulp serves as the basic long-fiber raw material for papermaking, constructing the mechanical framework of the paper and ensuring the dry and wet basic strength of the splicing paper to meet the requirements of high-speed cigarette rolling without breaking the paper; a large number of hydroxyl groups on the fiber surface can form hydrogen bonds with cationic transparent starch, sodium carboxymethyl cellulose, and polyamide epichlorohydrin wet strength agent, providing an attachment carrier for carboxylated cellulose nanofibers and functional additives; the long fibers intertwine to form a network of voids, which, together with the carboxylated cellulose nanofibers, fills the voids to achieve a highly transparent substrate, which is different from broad-leaved short fibers and balances strength and light transmission. When the amount of fully bleached softwood pulp added in the transparent thermochromic zone is less than 70 parts, the mechanical support skeleton of the paper constructed by long fibers is sparse, resulting in insufficient dry and wet basic strength of the paper sheet. This makes it prone to tearing and paper breakage during high-speed cigarette rolling. At the same time, the total number of hydroxyl sites on the fiber surface that can be used for hydrogen bonding and cross-linking anchoring agents is insufficient, making it difficult for cationic transparent starch, sodium carboxymethyl cellulose, polyamide epichlorohydrin wet strength agent, carboxylated cellulose nanofibers, and dual-temperature zone reversible thermochromic microcapsule powder to adhere and remain stably. This significantly deteriorates the pulp's filtration performance and makes dewatering of the wire section difficult. When the amount of fully bleached softwood pulp added in the transparent thermochromic zone is greater than 80 parts, the large number of fiber gaps formed by the interweaving of long fibers lack filling with ultrafine nanofibers. The scattered light from the air causes an increase in haze and a significant decrease in light transmittance in the transparent thermochromic zone, making it difficult to visually observe the internal structure of the filter rod. Furthermore, the ability of nanofibers to retain microcapsules is weakened, and a large amount of dual-temperature zone reversible thermochromic microcapsule powder is lost during dewatering, resulting in weak color development effect and reduced reversible cycle durability.
[0032] Furthermore, carboxylated cellulose nanofibers fill the microscopic gaps between the fibers of fully bleached softwood pulp, reducing light scattering caused by air in the fiber gaps and significantly improving the light transmittance of the paper surface, achieving a high transparency effect with a light transmittance of not less than 85% at room temperature. The surface of the carboxylated cellulose nanofibers is rich in hydroxyl and carboxyl groups, which can be firmly combined with fibers, cationic transparent starch, and sodium carboxymethyl cellulose through hydrogen bonds. At the same time, they physically embed and fix the dual-temperature zone reversible thermochromic microcapsule powder dispersed in the paper base. Combined with food-grade water-based acrylic resin to form a protective film on the outer layer of the microcapsules, the temperature-changing functional powder is anchored in multiple stages to inhibit the migration and precipitation of the temperature-changing core material. Meanwhile, the ultrafine nanofibers improve the density and wet tensile strength of the paper, solving the problem of insufficient strength of the high-transparency paper base. When the amount of carboxylated cellulose nanofiber added in the transparent thermochromic zone is less than 20 parts, there is a lack of sufficient ultrafine fiber to fill the microscopic gaps formed by the interweaving of fully bleached softwood pulp. The air in the gaps generates strong light scattering, the haze of the transparent thermochromic zone increases and the light transmittance decreases, making it impossible to achieve internal bead bursting and visual observation of the filter material. The surface has insufficient active sites that can provide hydrogen bonds and electrostatic adsorption, making it difficult to effectively anchor the dual-temperature zone reversible thermochromic microcapsule powder and sodium carboxymethyl cellulose. The functional components are severely lost during the forming and dehydration stage, which cannot fully improve the paper density and wet tensile strength. The thermochromic color is light and the function decays rapidly after multiple cycles. When the amount of carboxylated cellulose nanofibers added in the transparent thermochromic zone exceeds 30 parts, the water retention of the pulp and the viscosity of the system exceed the standard significantly, the dewatering efficiency of the wire section drops sharply, the moisture content of the wet paper blank is too high, continuous papermaking is prone to wire sticking, and the production stability decreases. Excessive nanofibers can easily cause pulp flocculation, resulting in an uneven surface in the transparent zone after forming and obvious burrs at the partition interface. It can also squeeze the interlacing space of the long fibers of fully bleached coniferous wood, weaken the dry strength of the paper, make it easy to break the paper during high-speed winding and splicing, and increase production energy consumption simultaneously, making it difficult to achieve stable large-scale production.
[0033] Furthermore, cationic transparent starch relies on positive charge electrostatic adsorption to the surface of negatively charged cellulose fibers (fully bleached softwood pulp fibers) and nanofibers (carboxylated cellulose nanofibers) to form a transparent film layer, reducing inter-fiber porosity, optimizing refractive index, and improving paper density and light transmittance; it also enhances inter-fiber bonding through hydrogen bonding, improving paper flexibility; it improves the retention rate of fine fibers and additives, reduces the loss of functional materials with white water, and lowers production costs. Cationic transparent starch at least partially neutralizes the negative charge on the fiber surface, making the fiber surface uniformly positively charged, which can form a polyelectrolyte electrostatic complex with subsequently added anionic sodium carboxymethyl cellulose, allowing the sodium carboxymethyl cellulose to stably fill the fiber voids. When the amount of cationic transparent starch added in the transparent thermochromic zone is less than 1.5 parts, it is difficult to fully coat the fibers, resulting in more pore residue and decreased light transmittance; the fiber bonding force is weak, and the paper is prone to brittle breakage; insufficient charge leads to poor complexation and fixation effect of sodium carboxymethyl cellulose, and serious loss of materials such as reversible thermochromic microcapsule powder in the dual-temperature zone; when the amount of cationic transparent starch added in the transparent thermochromic zone is greater than 2.5 parts, it will cause excessively high pulp viscosity, difficulty in dehydration, increased drying energy consumption, and the paper is prone to brittleness and sticking to the drying cylinder; charge imbalance disrupts the complexation effect with sodium carboxymethyl cellulose, free starch accumulation reduces light transmittance uniformity, and the retention rate of functional materials deteriorates. Among them, the cationic transparent starch is food-grade cassava-based cationic transparent starch.
[0034] Furthermore, sodium carboxymethyl cellulose, as an anionic dispersion stabilizer, inhibits the agglomeration of isoelectric carboxylated cellulose nanofibers by electrostatic repulsion, ensuring uniform dispersion of nanofibers; it fills micropores, further reducing haze, and synergistically forms polyelectrolyte complexes with cationic transparent starch, improving the light transmittance of the paper surface; at the same time, it plays a water-retaining role, slowing down the pulp dewatering rate, optimizing paper uniformity, and preventing uneven light transmittance in certain areas. When the amount of sodium carboxymethyl cellulose added in the transparent thermochromic zone is less than 0.3 parts, the nanofibers are prone to agglomeration and uneven dispersion, the fiber pores are not fully filled, the haze increases and the light transmittance decreases; the water retention and pulp stabilization capacity is insufficient, the pulp dewatering is too fast, the paper sheet uniformity is poor, the light transmittance in the transparent zone is uneven, and the complexation effect with cationic transparent starch is weak, resulting in insufficient synergistic improvement in strength and light transmittance; when the amount of sodium carboxymethyl cellulose added in the transparent thermochromic zone is more than 0.8 parts, the water retention and viscosity of the pulp will be greatly increased, the dewatering of the wire section will be hindered, and the drying energy consumption will increase; excessive anionic components will disrupt the charge balance, destroy the complexation system with cationic starch, and excess sodium carboxymethyl cellulose will accumulate freely, reducing the light transmittance uniformity in the transparent zone, and also easily causing the paper sheet to become brittle after drying.
[0035] Furthermore, food-grade sorbitol, as a plasticizing and moisturizing agent, can physically penetrate into the gaps between fibers and functional components in paper, reducing paper brittleness and improving overall flexibility. It can also bind with fully bleached softwood pulp fibers, cationic transparent starch, and sodium carboxymethyl cellulose through hydrogen bonds, maintaining a stable moisture content in the paper base and effectively preventing brittleness and cracking after drying and dehydration in the transparent thermochromic zone. If the amount of food-grade sorbitol added in the transparent thermochromic zone is less than 0.6 parts, the plasticizing and moisturizing effects are insufficient, making it difficult to fully bind with fibers, cationic transparent starch, and sodium carboxymethyl cellulose through hydrogen bonds. This results in paper that is prone to dehydration and brittleness, easily cracking during processing and use in the transparent zone, and failing to guarantee the paper's flexibility. If the amount of food-grade sorbitol added in the transparent thermochromic zone is greater than 1.0 part, excessive sorbitol significantly increases the pulp's water-holding capacity, hindering dehydration and drying. Excess sorbitol cannot completely form hydrogen bonds with fibers, cationic transparent starch, and sodium carboxymethyl cellulose, leaving free components in the paper that make the finished product prone to moisture absorption and softening. This also causes increased haze and decreased light transmittance in the transparent zone.
[0036] Furthermore, the internal core material of the dual-temperature zone reversible thermochromic microcapsule powder includes a leuco dye, bisphenol S color developer, and a long-chain phase change solvent. The outer wall of the dual-temperature zone reversible thermochromic microcapsule powder is coated with melamine-formaldehyde resin (i.e., melamine resin). The particle size of the dual-temperature zone reversible thermochromic microcapsule powder is 2-7 μm.
[0037] Specifically, the particle size of the dual-temperature zone reversible thermochromic microcapsule powder is controlled at 2-7 μm. The outer layer is coated with a melamine-formaldehyde transparent resin wall material with a coating thickness of 60-120 nm. The inner core material is composed of food-grade leuco dye, bisphenol S color developer, and two long-chain fatty acid ester compound phase change solvents. The low-temperature phase change solvent is hexadecyl tetradecanoate with a melting point of 45±1℃, and the high-temperature phase change solvent is octadecyl hexadecanoate with a melting point of 60±1℃. At room temperature, both long-chain fatty acid ester compound phase change solvents are solid. The solid medium physically isolates the leuco dye from the bisphenol S color developer, resulting in a colorless and transparent powder. The microcapsules themselves are also colorless and transparent, not interfering with the light transmittance of the paper substrate and ensuring good visibility at room temperature. When the temperature rises to 45 ℃, the low-temperature phase change solvent melts and liquefies. The dye and color developer come into contact and undergo a protonation ring-opening reaction, resulting in initial color development and a light hue. When the temperature continues to rise to 60 ℃, the high-temperature phase change solvent completely melts, significantly improving the fluidity of the core material system, resulting in a more complete color development reaction and a significantly deeper color. When the ambient temperature drops below the phase change temperature, the compound phase change solvent re-solidifies, isolating the color-developing components again. The dye molecules close their rings and lose color, and the coating returns to a colorless and transparent state. This microcapsule powder can achieve reversible color change with temperature fluctuations and has a reversible cycle life of ≥500 cycles.
[0038] In this embodiment, the dual-temperature zone reversible thermochromic microcapsule powder exhibits two-stage color-changing responses at 45℃ and 60℃. During inhalation and heating, it displays color in stages, providing direct feedback on the inhalation temperature and enabling visual warnings of the inhalation status. Combined with a transparent temperature-changing zone, it can also identify localized abnormal heating caused by filter rod capsule breakage, enabling online screening of defective products. The melamine-formaldehyde resin completely encapsulates the core material, preventing the migration of dyes and color developers, eliminating pigment smudging and precipitation issues, and meeting the safety standards for tobacco additives and food contact. The 2–7 μm size is suitable for wet papermaking systems, ensuring uniform pulp dispersion, low capsule breakage rate during papermaking, and stable color-changing performance. It can withstand over 500 repeated heating and cooling cycles without significant attenuation. When the amount of reversible thermochromic microcapsule powder added to the transparent thermochromic zone is less than 0.3 parts, the content of thermochromic functional components in the paper base is insufficient, resulting in weak color changes at 45℃ and 60℃, and an insignificant temperature warning effect. The low number of capsules per unit area also leads to poor identification of burst bead breakage warnings, and the functionality fails to meet design requirements. When the amount of reversible thermochromic microcapsule powder added to the transparent thermochromic zone is greater than 0.8 parts, excessive microcapsules crowd out the fiber interlacing space, reducing the dry and wet strength of the paper sheet, making it prone to breakage during high-speed winding. A large number of microcapsules also increases the solid content of the pulp, hindering pulp dewatering and increasing drying energy consumption. Excessive capsules can easily lead to localized agglomeration, uneven color changes in the transparent zone, and increased raw material costs.
[0039] This application utilizes the visualization of the transparent temperature-changing zone and the dual-stage temperature-changing characteristics to achieve early warning of filter rod capsule breakage. After the capsule inside the cigarette filter rod breaks, the internal oily liquid soaks into the surrounding filter fibers. During the smoking process, the local heat conduction in the damaged area is abnormal and the temperature is higher. The transparent area at the corresponding location of the breakage will show local discoloration in advance even at room temperature without smoking. In addition, during cigarette manufacturing, workers in cigarette factories can quickly screen out defective cigarettes with broken capsules by visual inspection.
[0040] This application allows for the replacement of different types of leuco dyes according to color requirements. While maintaining the phase change solvent, bisphenol S color developer, microcapsule wall material structure, and preparation process unchanged, dual-temperature zone reversible thermochromic microcapsules in different color systems, such as blue, red, and yellow-orange gradients, can be prepared. Specifically, the leuco dye used in the blue microcapsules is 3-diethylamino-6-methyl-7-chlorofluorane; the leuco dye used in the red microcapsules is 2-(2-hydroxy-4-diethylaminophenyl)naphthofuran; and the yellow-orange gradient microcapsules use a compound of yellow fluoranes as the leuco dye. In a preferred embodiment of this application, the dual-temperature zone reversible thermochromic microcapsule powder used in cigarette tipping paper is a compound yellow-orange gradient microcapsule. When the temperature rises to 45°C, the microcapsules change from colorless and transparent to light yellow; when the temperature rises to 60°C, the color deepens further, appearing orange-red; when the temperature drops below the phase change temperature, the microcapsules can quickly return to a colorless and transparent state, demonstrating excellent color reversibility.
[0041] In another embodiment of this application, blue dual-temperature zone reversible thermochromic microcapsule powder is selected as the functional raw material, and the remaining process parameters and preparation process are the same as those in the preferred embodiment of this application. Testing showed that the light transmittance of the functional transparent area of the finished cigarette tipping paper at room temperature was 88%, and the paper surface was uniformly transparent, free of impurities and particle agglomeration defects. When the ambient temperature was raised to 45°C, the transparent area of the paper surface stably displayed a light blue hue; with further heating to 60°C, the color reaction became more complete, and the color deepened significantly, presenting a deep blue; when the ambient temperature dropped below the room temperature phase transition temperature, the phase transition solvent inside the microcapsules re-solidified, isolating the color-developing components, and the paper surface color gradually faded, restoring its initial colorless and transparent state.
[0042] In another embodiment of this application, red-based dual-temperature-zone reversible thermochromic microcapsule powder is selected as the functional raw material, and the remaining process parameters and preparation procedures are the same as those in the preferred embodiment of this application. The finished cigarette tipping paper has excellent high light transmittance at room temperature, and the paper surface is clean and transparent. When the temperature rises to 45°C, the paper surface stably presents a light red color; when the temperature rises to 60°C, the color intensity deepens, turning into a more saturated deep red; after cooling to room temperature, it reversibly returns to a colorless and transparent state.
[0043] Furthermore, after drying, food-grade acrylic resin can uniformly coat the dual-temperature zone reversible thermochromic microcapsule powder and form a protective film, avoiding microcapsule damage and internal color component migration and precipitation caused by papermaking, pressing, and drying processes. At the same time, relying on its own film-forming structure, it stably anchors the microcapsules in the fiber network, reducing the loss of thermochromic functional materials. The resin is a food-grade raw material, which meets the food contact safety standards for tobacco auxiliary materials, and is matched with limited solid content, viscosity and glass transition temperature parameters. The low-temperature film-forming curing of the resin will not destroy the reversible color-changing system of the microcapsules, and can also slightly fill the fine pores of the paper base, optimizing the light transmission uniformity of the transparent thermochromic zone. When the amount of food-grade water-based acrylic resin added in the transparent thermochromic zone is less than 0.2 parts, the ability of the food-grade acrylic resin to coat and anchor the reversible thermochromic microcapsule powder in both temperature zones is insufficient. The microcapsules are easily damaged and leaked during the pressing and drying processes, and the color-developing components migrate and bleed. At the same time, the microcapsule retention rate decreases, the color change in the transparent thermochromic zone is light and uneven, and the lack of a surface film to fill the micropores of the paper base results in poor light transmission consistency. When the amount of food-grade water-based acrylic resin added in the transparent thermochromic zone is more than 0.4 parts, the excess resin significantly increases the viscosity and water retention of the pulp, increases the difficulty of dewatering the wire section, and increases the drying energy consumption. Excess resin accumulates in large quantities in the fiber gaps, increases light scattering, reduces the light transmittance of the transparent thermochromic zone, and also makes the paper hard and brittle, making it easy to break when cigarettes are rolled at high speed.
[0044] Furthermore, the food-grade waterborne acrylic resin has a solid content of 40%–46%, a viscosity of 800–1500 mPa·s at 25°C, and a glass transition temperature (Tg) of 10–25°C. Limiting the solid content to 40%–46% ensures that the food-grade acrylic resin possesses sufficient film-forming components to completely encapsulate the dual-temperature-zone reversible thermochromic microcapsule powder. This prevents incomplete protective films due to insufficient effective resin and avoids slurry thickening and clumping due to excessive solid content. The viscosity at 25°C is controlled at 800–1500 mPa·s. Within the s range, the resin exhibits moderate dispersion and fluidity in the slurry, allowing it to adhere uniformly to the surface of the microcapsules. This prevents uneven coating due to excessively low viscosity and localized resin agglomeration due to excessively high viscosity. With a glass transition temperature (Tg) set between 10 and 25°C, the resin can form a film slowly at low temperatures under the gradient drying temperature conditions of this invention. This avoids the need for high-temperature curing due to excessively high Tg, which could damage the phase transition and color-changing system inside the microcapsules, and also prevents the resin film from becoming soft and susceptible to moisture due to excessively low Tg, thus stably maintaining the long-lasting reversible color-changing performance of the microcapsules.
[0045] Furthermore, the polyamide epichlorohydrin wet strength agent contains a nitrogen-containing heterocyclic butyl quaternary ammonium groups, which can covalently crosslink with the carboxyl groups on the surface of fully bleached softwood pulp fibers and carboxylated cellulose nanofibers, forming a dense water-resistant network through intermolecular self-crosslinking, which significantly improves the wet tensile strength of the paper. The crosslinked network can encapsulate and fix the dual-temperature zone reversible thermochromic microcapsule powder, improving the retention stability of the temperature-changing functional components in the paper base. When the amount of polyamide epichlorohydrin wet strength agent added in the transparent thermochromic zone is less than 0.8 parts, the cross-linking active groups are insufficient, making it difficult to form a complete waterproof network, resulting in low paper wet strength. The binding effect on the dual-temperature zone reversible thermochromic microcapsule powder is weak, and more microcapsules are lost during papermaking. The finished product is easily deformed after contact with moisture, and the color change effect is uneven. When the amount of polyamide epichlorohydrin wet strength agent added in the transparent thermochromic zone is more than 1.5 parts, the excessive polyamide epichlorohydrin wet strength agent carries a large number of cationic groups. The large number of cationic groups breaks the polyelectrolyte complexation balance between cationic transparent starch and sodium carboxymethyl cellulose, causing the pulp to flocculate and agglomerate, and reducing the uniformity of light transmission in the transparent zone. The pulp dewatering slows down, the drying energy consumption increases, and the excessive cross-linking makes the paper brittle and hard, making it easy to tear and break the paper during high-speed winding and splicing. Of course, an alternative is to replace 30% of the 1.2 parts of polyamide epichlorohydrin wet strength agent in the transparent thermochromic zone component with a soybean protein-based environmentally friendly crosslinking agent, while keeping the other components in the transparent thermochromic zone, the opaque zone components, and the preparation process unchanged. The resulting cigarette tipping paper has a wet tensile strength of 9.0 kN / m, and the soil composting degradation cycle is shortened by 12%, further improving the all-plant-based biodegradability and meeting the demand for high-end environmentally friendly cigarette additives.
[0046] Furthermore, amphoteric polyacrylamide, possessing both anionic and cationic groups, can synergistically regulate the charge balance of the pulp with cationic transparent starch and polyamide epichlorohydrin wet strength agent within the system. It can also flocculate fine fibers, carboxylated cellulose nanofibers, and dual-temperature zone reversible thermochromic microcapsule powder, significantly improving the retention rate of various functional components, reducing material loss with white water, and lowering raw material consumption. At the same time, it improves the pulp's water filtration performance, accelerates the dewatering speed of the wire section, shortens drying time, saves production energy, and optimizes paper uniformity, ensuring that the light transmission and color-changing effect in the transparent thermochromic zone are uniform overall. When the amount of amphoteric polyacrylamide retention aid added in the transparent thermochromic zone is less than 0.05 parts, the flocculation effect is weak, and it is difficult for fine fibers and dual-temperature zone reversible thermochromic microcapsule powder to aggregate effectively. A large amount of functional materials are lost with the dewatering white water, and the color change in the transparent thermochromic zone is light and uneven. The pulp filtration efficiency is poor, the moisture content of the wet paper blank is high, the drying energy consumption increases, the paper uniformity is poor, and there are obvious differences in local light transmission. When the amount of amphoteric polyacrylamide retention aid added in the transparent thermochromic zone is more than 0.15 parts, the excessive amphoteric polyacrylamide will cause excessive flocculation of the pulp, forming large-sized flocs. After molding, the surface of the transparent thermochromic zone is uneven, the haze increases, and the light transmission performance decreases. The charge imbalance of the pulp system destroys the polyelectrolyte complex structure of cationic transparent starch and sodium carboxymethyl cellulose, the pore filling effect is poor, and the flocs inside the paper are unevenly distributed, making it easy for local brittleness to occur during high-speed winding.
[0047] In a preferred embodiment of this application, the opaque region comprises the following components in parts by weight: 90 parts of fully bleached hardwood pulp, 10 parts of fully bleached softwood pulp, 20 parts of heavy calcium carbonate, 1.5 parts of cationic starch, 0.2 parts of alkyl ketene dimer sizing agent, 1.0 part of polyamide epichlorohydrin wet strength agent, and 0.1 parts of amphoteric polyacrylamide retention aid; wherein the particle size D50 of the heavy calcium carbonate is ≤0.8μm.
[0048] Specifically, firstly, a blended fiber system consisting of 90 parts fully bleached hardwood pulp and 10 parts fully bleached softwood pulp is used to achieve a balance between paper uniformity, smoothness, and mechanical toughness. The high proportion of hardwood pulp, as the main substrate, features fine, soft, and densely interwoven fibers, resulting in a smooth and delicate paper surface. This significantly reduces surface roughness and microscopic pinhole defects, leading to excellent paper uniformity. Simultaneously, the fine and uniform microscopic voids formed by the interwoven fibers provide ideal filling sites for subsequent ultrafine heavy calcium carbonate fillers. Multiple light scattering effectively enhances paper opacity and maintains excellent whiteness, making it suitable for subsequent printing, hot stamping, and other deep processing techniques in cigarette tipping paper. Furthermore, the lower cost of hardwood pulp raw materials effectively controls product production costs. A small amount of long coniferous wood fibers are evenly interspersed within the network of short hardwood fibers, forming a stable mechanical framework for the paper. This precisely compensates for the poor toughness and brittleness of pure hardwood pulp paper, significantly improving the dry strength and folding endurance of the paper. It effectively prevents paper breakage, tearing, and damage during high-speed cigarette rolling, slitting, and hot-pressing processes, while maintaining both finished product appearance quality and production stability. It should be noted that the total amount of fully bleached hardwood pulp and fully bleached coniferous wood pulp in the opaque area is 100 parts. When the hardwood pulp content is below 80 parts and the softwood pulp content is above 20 parts, the proportion of long fibers is too high, resulting in larger interwoven pores, decreased paper surface smoothness, increased roughness, poor uniformity of ultrafine heavy calcium carbonate filling, reduced paper opacity, and deterioration of printing smoothness and appearance. Simultaneously, raw material costs increase significantly. When the hardwood pulp content is above 95 parts and the softwood pulp content is below 5 parts, the long fiber skeleton is severely insufficient, leading to poor paper toughness, increased brittleness, and decreased dry strength and folding endurance. This makes the paper prone to breakage, tearing, and cracking during high-speed cigarette rolling, slitting, and hot-pressing processes, failing to meet the requirements of high-speed machine operation. The proportions within this range can stably form a double-layer structure of "dense short fiber film formation + long fiber skeleton reinforcement," balancing high paper surface uniformity and finished product mechanical stability. The cationic starch can be ordinary papermaking cationic starch based on corn or cassava.
[0049] Secondly, adding 20 parts of ultrafine paper-specific heavy calcium carbonate (GCC) with a D50 ≤ 0.8μm as the core light-blocking filler significantly improves the light-blocking performance of opaque areas and the paper surface processing performance. The ultrafine paper-specific heavy calcium carbonate particles can uniformly fill the microscopic pores formed by interwoven fibers, effectively blocking light penetration channels. Through the multiple light scattering effects at the particle-air interface, the paper's light-blocking rate is greatly improved, completely eliminating problems such as light-transmitting white spots and localized light penetration. This results in uniform and full coverage of opaque areas with consistent color, forming a clear and contrasting visual partition with the central transparent temperature-changing area, solving the drawbacks of blurred partitioning and poor coverage consistency in traditional tipping paper. Simultaneously, the ultrafine particle size filler optimizes paper surface smoothness and fineness, improves ink adhesion substrate conditions, significantly enhances the printability of tipping paper, ensures uniform printing color and firm adhesion, and effectively improves the finished product's appearance and texture. When the amount of heavy calcium carbonate is less than 15 parts, the fiber pores are not adequately filled, the microscopic light-transmitting channels of the paper base cannot be completely blocked, resulting in weak light scattering ability, low opacity, and a tendency for localized light transmission and white spots to show through, with blurred boundaries between the transparent and temperature-sensitive areas. When the amount of heavy calcium carbonate is greater than 25 parts, excessive filling of inorganic fillers crowds out fiber bonding sites, significantly weakening the inter-fiber bonding force, causing a simultaneous decrease in both dry and wet strength of the paper, increased brittleness, and poorer folding endurance. At the same time, the pulp's water filtration performance deteriorates, the wire section is prone to sticking to the cylinder, the filler retention rate decreases, and production stability deteriorates. The range of 15 to 25 parts can maximize light scattering efficiency and achieve a uniform high-coverage effect without damaging the paper's mechanical properties.
[0050] Furthermore, 1.5 parts of cationic starch can enhance the bonding between fibers and improve the surface properties of paper. Its cationic groups are electrostatically adsorbed onto the negatively charged fiber surface and strengthen the bonding force between fibers through hydrogen bonds, thereby improving the dry strength and structural density of the paper, optimizing the paper surface smoothness, and thus improving the adaptability of subsequent printing and hot stamping processes. At the same time, its regulatory effect on the surface charge of fibers, in conjunction with the retention aid system, improves the retention rate of fillers and microfibers, effectively reducing material loss with white water during production and reducing raw material loss. When the amount of cationic starch is less than 1.0 part, the electrostatic adsorption capacity for negatively charged fibers and heavy calcium carbonate fillers is insufficient, resulting in a large loss of microfibers and fine fillers, poor paper uniformity, uneven coverage, and low dry strength. When the amount of cationic starch is more than 2.0 parts, the cationic charge of the system is excessive, the pulp is prone to excessive flocculation, flocculent and cloudy spots appear on the paper surface, the smoothness decreases, and the paper's hydrophilicity is too high, weakening its resistance to water vapor penetration.
[0051] Meanwhile, 0.2 parts of alkyl ketene dimer (AKD) sizing agent impart excellent water resistance to the paper. During the paper drying and forming process, the long-chain alkyl groups of the alkyl ketene dimer sizing agent are directionally spread on the fiber surface to form a low surface energy hydrophobic layer. At the same time, its lactone rings are covalently bonded to the fiber hydroxyl groups, firmly anchoring the hydrophobic groups to the fiber surface. This effectively blocks the penetration and erosion of cigarette adhesive, oral saliva, and smoke moisture, preventing the paper from absorbing water, softening, wrinkling, deforming, and losing strength. It ensures dimensional stability and structural regularity after the feed paper is attached to the filter rod, and prevents bottom penetration and damage under long-term smoking conditions, while maintaining stable light-blocking performance in the opaque area. When the amount of alkyl ketene dimer is less than 0.1 parts, the hydrophobic coating on the fiber surface is incomplete, and it cannot effectively resist the penetration of oral saliva, smoke vapor, and cigarette adhesive. The paper is prone to absorbing water, becoming soft, wrinkled, deformed, and showing through when wet, and its light-blocking stability decreases. When the amount of alkyl ketene dimer is more than 0.3 parts, the excessive free alkyl ketene dimer sizing agent will reduce the fiber bonding force, causing the paper strength to decrease. In addition, the surface energy of the paper is too low, which seriously affects the adhesion of ink and hot stamping materials, resulting in printing defects and coating peeling.
[0052] Furthermore, 1.0 part of polyamide epichlorohydrin (PAE) wet strength agent precisely balances the wet strength and flexibility of the paper. The nitrogen-containing heterocyclic butyl quaternary ammonium groups in the polyamide epichlorohydrin wet strength agent molecule can covalently crosslink with the carboxyl groups on the surface of wood pulp fibers, while simultaneously undergoing intermolecular self-crosslinking, constructing a stable and dense water-resistant three-dimensional network structure. This significantly improves the wet tensile strength of the paper, allowing the opaque areas to withstand long-term immersion in saliva and cigarette adhesive without softening or breaking, perfectly adapting to the high-speed rolling and splicing production conditions of cigarette factories. This addition amount is within the optimal critical range, avoiding the defects of insufficient wet strength and easy paper collapse caused by low dosage, while also avoiding the problems of paper hardening, brittleness, and decreased flexibility caused by excessive crosslinking by high dosage, ensuring that the finished product has both high strength and excellent feel. When the amount of polyamide epichlorohydrin wet strength agent is less than 0.8 parts, the fiber cross-linking network is sparse, the wet tensile strength is insufficient, and the paper is easy to soften and fall apart after being soaked in saliva and glue, and cannot withstand high-speed winding conditions; when the amount of polyamide epichlorohydrin wet strength agent is more than 1.2 parts, the system is over-cross-linked, the fiber network is too rigid, the paper becomes hard and brittle, the flexibility is significantly reduced, the finished product is easy to crack when bent and has a stiff feel.
[0053] Finally, 0.1 parts of amphoteric polyacrylamide retention aid effectively optimizes pulp forming performance and finished product uniformity. Through a dual action of charge neutralization and polymer bridging flocculation, the amphoteric polyacrylamide retention aid efficiently captures fine fibers, ultrafine calcium carbonate microparticles, and other fine materials in the pulp, further improving the retention rate of fine materials and reducing white water material loss. Simultaneously, it can uniformly control the flocculation state of the pulp, stabilize the uniformity of pulp forming on the wire, effectively avoid problems such as uneven whiteness, opacity, and strength on the paper surface, ensure uniform performance in the opaque area of the entire sheet, and improve batch stability. When the amphoteric polyacrylamide retention aid is less than 0.05 parts, the charge neutralization and bridging flocculation capabilities are insufficient, resulting in severe loss of ultrafine heavy calcium carbonate, fine fibers, and functional additives, low material retention, and poor uniformity of paper whiteness, hiding power, and strength. When the amphoteric polyacrylamide retention aid is more than 0.15 parts, excessive polymer bridging leads to intense pulp flocculation, resulting in defects such as clumps, pinholes, and uneven thickness on the paper surface, and decreased batch consistency. The range of 0.05 to 0.15 parts can achieve moderate and uniform flocculation, maintaining excellent paper uniformity while ensuring high retention rate.
[0054] In this embodiment, the opaque area uses a high proportion of broadleaf short fibers as the main forming body and a small amount of coniferous long fibers as the mechanical reinforcement skeleton to construct a paper base matrix with excellent uniformity and balanced strength. Utilizing an optimal amount of ultrafine heavy calcium carbonate to fill the fiber pores enhances the light scattering effect, achieving a uniform, high-coverage opaque effect and forming a visually distinct zone with clear boundaries from the transparent temperature-sensitive area. A highly efficient retention system is constructed using cationic starch in synergy with amphoteric polyacrylamide, improving the retention rate of fillers and microfibers and optimizing paper surface smoothness and dry strength. An alkyl ketene dimer sizing system is used to construct a stable hydrophobic layer, giving the paper base excellent water resistance and impermeability, avoiding wet deformation and bottom-penetration defects. Combined with a polyamide-epoxychloropropane wet-strength agent to cross-link and form a water-resistant three-dimensional network, the paper's wet strength and flexibility are precisely balanced, ensuring structural stability and resistance to damage under conditions of saliva, glue impregnation, and high-speed winding. The components work synergistically and complement each other, giving the opaque area the characteristics of high opacity, high uniformity, water and moisture resistance, strong and balanced strength, and excellent printability, fully meeting the needs of cigarette appearance zoning display, deep processing printing, and high-speed industrial production.
[0055] The present invention also provides a method for preparing the aforementioned temperature-sensitive color-changing cigarette tipping paper, comprising the following steps: Prepare transparent thermochromic slurry and opaque slurry separately; Transparent thermochromic pulp and opaque pulp are simultaneously fed into the web through a partitioned dual-channel headbox and arranged alternately in fixed width units. After being dewatered by gradient negative pressure, the fibers of the two zones naturally interweave to form an integrated wet paper blank. The wet paper blank is dehydrated by ambient temperature boot press; A three-stage gradient drying process with progressively decreasing temperature is used to control the moisture content of the paper. The transparent thermochromic areas of the paper are soft-calendered, while the opaque areas are left uncalendered. The paper is then slit and rewound under low tension to obtain the finished product.
[0056] This application describes a method for preparing thermochromic cigarette tipping paper. It employs a dual-zone pulp synchronous online forming process, where the transparent thermochromic zone pulp and the opaque zone pulp are independently mixed and then synchronously online and alternately arranged in a dual-channel headbox. The fibers of the two zones naturally interweave at the boundary, forming an integrated paper blank structure without adhesive interfaces. This fundamentally eliminates defects in traditional lamination and compounding processes, such as weak interlayer bonding, delamination, edge curling, and peeling caused by adhesive aging and wet penetration. The finished product exhibits clear and regular zone boundaries and a stable and reliable overall structure. The process is complemented by a room-temperature boot press dewatering and a three-stage gradient drying temperature control system. This system avoids premature triggering and failure of the thermochromic function during production. The gentle room-temperature pressing avoids high-temperature thermal shock, and the gradient low-temperature drying consistently keeps the internal temperature of the paper base below the trigger temperature of the dual-zone reversible thermochromic microcapsule powder. This completely eliminates problems such as premature color development, performance failure, and finished product scrap caused by production thermal history, ensuring that the product's thermochromic response function is precisely triggered only during the usage phase. Simultaneously, a differentiated zoned calendering process is employed, with only the transparent thermochromic areas undergoing soft calendering. Leveraging the gentle pressure of soft calendering, the paper surface is moderately leveled, and micropores are refined, effectively improving the paper's smoothness, density, and light transmission uniformity. This enhances the visual contrast of thermochromic color changes without causing excessive crushing and paper brittleness. The opaque areas are treated without calendering, fully preserving the microscopic rough structure of the fibers and the light scattering system of the heavy calcium carbonate filler. This maximizes the paper's opacity and opacity, balancing the visible thermochromic effects of the transparent areas with the compatibility with printing, hot stamping, and other deep processing in the opaque areas. Subsequent low-tension slitting and rewinding processes effectively avoid defects such as paper stretching deformation and stress whitening, ensuring dimensional accuracy and paper quality in the finished product, perfectly adapting to the high-speed cigarette rolling production conditions. Furthermore, this preparation process relies on the existing papermaking equipment system, requiring only targeted modifications to the headbox and calendering module, resulting in low equipment modification costs and strong applicability. The raw and auxiliary materials used are all common bulk materials in the industry, with stable sources and high cost performance. At the same time, it eliminates cumbersome processes such as traditional offline lamination and secondary coating, simplifies the production process, significantly improves the yield of mass-produced products, effectively reduces the overall production cost, and has excellent process compatibility and stability for large-scale mass production.
[0057] In some embodiments, the step of preparing the transparent thermochromic slurry includes: Fully bleached softwood pulp was diluted in deionized water to a disintegration concentration of 3.5%–4.0%. The fibers were then broken down in a pulper until completely dispersed without fiber bundles. Carboxylated cellulose nanofibers were then added and mixed evenly to obtain a transparent thermochromic mixed pulp. The transparent thermochromic mixed pulp was then placed in a high-consistency refiner and refined at an input concentration of 3.8%–4.2%. The pulp freeness was controlled at 92±3°SR and the average fiber length was 0.8–1.0 mm to obtain a transparent thermochromic fiber-based pulp. Under stirring conditions of 800-1000 rpm, cationic transparent starch, sodium carboxymethyl cellulose, food-grade sorbitol, polyamide epichlorohydrin wet strength agent, and amphoteric polyacrylamide retention aid are added sequentially to the transparent thermochromic fiber-based slurry. After each component is added, it is stirred and matured separately to ensure that the additives are fully dispersed and adsorbed, thus forming a transparent slurry modified with additives. The dual-temperature zone reversible thermochromic microcapsule powder and food-grade waterborne acrylic resin were premixed and dispersed evenly at room temperature. After the aforementioned additives were matured in stages, the stirring speed was reduced from 800-1000 rpm to 500 rpm under low shear stirring. Then, the dual-temperature zone reversible thermochromic microcapsule powder and food-grade waterborne acrylic resin functional materials were slowly added into the transparent slurry modified by the additives. After functional modification, the transparent slurry is diluted with deionized water to a net concentration of 0.9%, stirred evenly, and then sealed and allowed to stand for 20-30 minutes to mature. The carboxylated cellulose nanofibers in the system form a dense nano-retention network, which, together with food-grade waterborne acrylic resin, forms a film on the surface of the microcapsules to increase the equivalent particle size. The synergistic effect of amphoteric polyacrylamide polymer bridging helps to retain the reversible thermochromic microcapsule powder in two temperature zones, significantly reducing the loss rate of the microcapsule network.
[0058] In a preferred embodiment of this application, a measured amount of deionized water is added to a pulper, and the fully bleached softwood pulp is placed in the deionized water to adjust the pulp concentration to 3.5%–4.0%. The pulp is then stirred and broken down for 15–20 minutes until the pulp lumps are completely dispersed and no fiber bundles remain. After breaking down, carboxylated cellulose nanofibers are added, and the mixture is stirred in a sealed container for 5 minutes to obtain a transparent thermochromic mixed pulp. The sealed mixing avoids the introduction of large amounts of air during stirring, thus preventing foam formation. Short-time mixing ensures uniform dispersion of the fully bleached softwood fibers and carboxylated cellulose nanofibers, forming preliminary hydrogen bonds, while maintaining a stable pulp concentration. The transparent thermochromic mixed pulp is then pumped into a high-consistency refiner, with the initial concentration controlled at 3.8%–4.0%. The pulping process, with a yield of 4.2%, employs a three-stage progressive refining process consisting of coarse refining, medium refining, and fine refining. Refining parameters and freeness are monitored throughout the process, with a stable freeness of 92±3°SR, achieving a transparent, temperature-sensitive fiber-based pulp. This refining process promotes the full fibrillation of the bleached coniferous long fibers, exposing a large number of free hydroxyl groups on the fiber surface, significantly increasing the fiber's specific surface area. This provides ample active sites for subsequent electrostatic adsorption and covalent cross-linking reactions of various additives. Simultaneously, the well-organized long fiber interwoven network stably binds carboxylated cellulose nanofibers, ensuring uniform dispersion of the nanofibers and effectively reducing the light scattering effect of air between fibers. This lays the core structural foundation for the finished product's highly transparent and uniform paper base.
[0059] Furthermore, the average fiber length is between 0.8 and 1.0 mm because this range can balance pulp forming stability, paper mechanical properties, substrate transparency, and the protective effect of dual-temperature zone reversible thermochromic microcapsule powder, resulting in the best overall performance. If the fiber length is greater than 1.0 mm, the fiber is prone to flocculation and clumping, which will cause paper surface turbidity, uneven forming, and easy paper cracking. It can also easily puncture the microcapsules, leading to thermochromic failure. If the fiber length is less than 0.8 mm, there will be too many fine fibers, which will easily cause poor water filtration, reduced production stability, paper brittleness and powder shedding. At the same time, it will adsorb and wear down the microcapsules, reduce the color development effect, and consume additives.
[0060] Furthermore, after grinding, the entire transparent thermochromic fiber-based slurry is transferred to the mixing tank. The stirring speed is maintained at 900 rpm throughout the process. The cationic transparent starch, sodium carboxymethyl cellulose, food-grade sorbitol, polyamide epichlorohydrin wet strength agent, and amphoteric polyacrylamide retention aid are added slowly in a fixed order. Each type of additive is stirred and matured separately after addition, forming a transparent slurry modified with the additives. This step-by-step, graded addition and maturation method completely avoids problems such as charge competition, mutual antagonism, and flocculation instability caused by the simultaneous addition of multiple additives. It allows each modified component to be adsorbed, reacted, and solidified layer by layer in an orderly manner, resulting in a clear hierarchy of action and stable modification effects.
[0061] Step 1: Add cationic transparent starch Cationic transparent starch was pre-mixed with 40℃ deionized water to prepare a 10% starch solution, which was then slowly and uniformly added to the mixing tank. After addition, the mixture was continuously stirred and matured for 5 minutes. The cationic component rapidly adsorbed onto the surface of negatively charged fully bleached softwood pulp fibers and carboxylated cellulose nanofibers through electrostatic attraction, preferentially occupying all effective adsorption sites on the fibers, building a strong and dry bonding framework and filling the micropores. Adding starch in advance reserved adsorption sites, preventing subsequent anionic additives from competing for the active sites on the fiber surface, and ensuring that the starch fully exerts its adsorption and reinforcing effect.
[0062] Step 2: Add sodium carboxymethyl cellulose Sodium carboxymethyl cellulose was dissolved in water at room temperature to prepare a 5% aqueous solution, which was then slowly added dropwise. After addition, the mixture was continuously stirred and allowed to mature for 10 minutes. As an anionic dispersion stabilizer, sodium carboxymethyl cellulose can fill the tiny pores not covered by cationic transparent starch. At the same time, it effectively inhibits the agglomeration of carboxylated cellulose nanofibers by relying on intermolecular electrostatic repulsion, significantly improving the overall dispersion uniformity of the pulp and further optimizing the basis for uniform light transmission in the transparent area of the paper.
[0063] Step 3: Add food-grade sorbitol Food-grade sorbitol is slowly and evenly added, stirred, and kept warm for 10 minutes. Sorbitol can penetrate into the amorphous areas of the fiber, exerting excellent plasticizing, anti-brittleness, moisture retention, and water stabilization effects. It effectively improves the flexibility of the paper base, balances the hydrophilic properties of the pulp system, and prevents the finished product from absorbing water and turning white, becoming brittle and deformed due to contact with oral saliva, smoke, and moisture. It also stabilizes the optical properties and structural toughness of the transparent area.
[0064] Step 4: Add polyamide epichlorohydrin wet strength agent The water-based polyamide epichlorohydrin wet strength agent stock solution is slowly and continuously added, and stirred for 15 minutes for cross-linking and maturation. The nitrogen-containing heterocyclic butyl quaternary ammonium active groups in the wet strength agent can stably covalently cross-link with the carboxyl groups on the surface of fibers and carboxylated cellulose nanofibers, gradually building a stable and dense water-resistant three-dimensional network structure, effectively improving the wet strength and structural stability of the paper, and avoiding defects such as softening and breakage of the paper base under wet immersion.
[0065] Step 5: Add amphoteric polyacrylamide retention aid The amphoteric polyacrylamide retention aid is diluted to a 0.1% solution in advance and sprayed onto the material at a low speed, followed by stirring and maturation for 10 minutes. The retention aid is added only after the fiber modification, dispersion plasticizing, and cross-linking reinforcement processes are completed. This allows for precise capture of free fine fibers and micro-functional particles in the slurry through the dual effects of charge neutralization and polymer bridging flocculation, efficiently constructing a stable retention system and significantly reducing the white water loss rate of fine materials. It effectively avoids the problems of multiple aids agglomerating and settling, uneven slurry flocculation, and large fluctuations in finished product performance caused by premature addition of the retention aid.
[0066] Furthermore, after all the basic additives have been modified and matured, and the performance of the slurry system has stabilized, the functional components of the dual-temperature zone reversible thermochromic microcapsule powder are gently added. The dual-temperature zone reversible thermochromic microcapsule powder is pre-mixed and dispersed with food-grade water-based acrylic resin at room temperature for 5 minutes to prepare a uniform and stable functional mixture. This effectively avoids the problems of local agglomeration and uneven dispersion caused by direct addition of microcapsule powder. Then, the stirring speed of the mixing vessel is reduced to 500 rpm under low-shear gentle stirring conditions, and the pre-mixed functional mixture is slowly added. Stirring is continued at a constant temperature for 10 minutes, with stirring done entirely in the dark. The slurry is stored in the dark. This low-shear, low-speed stirring environment completely avoids high-shear impact and tearing that could damage the outer resin wall of the microcapsules, preventing problems such as capsule rupture, core material leakage, and functional failure. This ensures that the dual-temperature zone reversible thermochromic microcapsule powder is completely and uniformly dispersed in the slurry system, stably retaining its reversible temperature response performance.
[0067] Furthermore, under continuous low-speed stirring at 500 rpm, deionized water was added in stages to dilute the fully dispersed functional slurry, while the slurry concentration was monitored online in real time. The slurry was precisely controlled to a standard on-board concentration of 0.9%, stirred evenly, and then sealed and allowed to stand for later use. This precisely controlled low on-board concentration system allows the functional microparticles of coniferous long fibers, carboxylated cellulose nanofibers, and fully encapsulated dual-temperature zone reversible thermochromic microcapsule powder to fully expand and disperse evenly, ensuring a smooth and uniform deposition of the slurry on the on-board. This effectively avoids defects such as cloudiness, color difference, and uneven thickness on the paper surface, and significantly improves the uniformity of light transmission in the transparent thermochromic zone and batch consistency.
[0068] In some embodiments, the step of preparing the opaque slurry includes: Fully bleached hardwood pulp and fully bleached softwood pulp were mixed and adjusted to a disintegration concentration of 4.0% in deionized water. The pulp was then disintegrated in a pulper until completely dispersed to obtain an opaque mixed pulp. The opaque mixed pulp was then beating with a double-disc refiner to control the beating degree of the pulp at 40±3°SR, thus obtaining an opaque fiber-based pulp. At a stirring speed of 800-1000 rpm, heavy calcium carbonate, cationic starch, alkyl ketone dimer sizing agent, polyamide epichlorohydrin wet strength agent, and amphoteric polyacrylamide retention aid are added sequentially to the opaque fiber-based slurry. After each component is added, it is stirred and matured separately to ensure that the additives are fully dispersed and adsorbed, thus forming an opaque slurry modified with additives. The modified opaque slurry was diluted with deionized water to a concentration of 1.2% for online processing. After stirring evenly, it was sealed and allowed to stand for 20-30 minutes to mature.
[0069] In a preferred embodiment of this application, a quantitative amount of deionized water is added to the pulper, and fully bleached hardwood pulp and fully bleached softwood pulp are mixed in a ratio of 9:1 in the deionized water to adjust the pulping concentration to 4.0%. Pulping is continued until the fibers are completely dispersed without pulp lumps, resulting in an opaque mixed pulp, achieving uniform mixing and interweaving of the two types of fibers. Subsequently, the opaque mixed pulp is fed into a double-disc refiner for conventional pulping, controlling the freeness at 40±3°SR, to obtain an opaque fiber-based pulp. This low freeness allows the short hardwood fibers to be moderately fibrillated, fully exposing the surface hydroxyl groups, improving the fiber hydrogen bonding force and paper density, while completely preserving the original length of the long softwood fibers, building a stable paper mechanical framework, and avoiding paper breakage defects during slitting and winding. The fibers are not excessively fine-fibrillated, and a large number of uniform pores are retained inside the network, providing sufficient filling space for ultrafine heavy calcium carbonate with D50≤0.8μm, and achieving a high opacity effect by relying on the multiple light scattering of the filler.
[0070] Further, after grinding, all the opaque fiber-based slurry is transferred to a mixing tank, and stirring is started at 900 rpm. The slurry is added in a fixed sequence: heavy calcium carbonate, cationic starch, alkyl ketone dimer sizing agent, polyamide epichlorohydrin wet strength agent, and amphoteric polyacrylamide retention aid. Each addition is cured separately in stages after each addition, forming an opaque slurry modified with the additives. This step-by-step addition method avoids the problems of charge competition and mutual interference between different components, allowing various additives to work in stages and synergistically enhance their effects.
[0071] Step 1: Add heavy calcium carbonate Ultrafine heavy calcium carbonate for papermaking is slowly added to the slurry system and stirred continuously for 5 minutes. This allows the calcium carbonate particles to be evenly dispersed and embedded in the fiber gaps, preventing filler agglomeration and blocking light penetration channels at the paper base structure level. This provides a stable light-blocking effect for the paper and simultaneously optimizes the smoothness and fineness of the paper surface, providing an excellent base for subsequent printing and hot stamping processes.
[0072] Step 2: Add cationic starch Add cationic starch and stir for 5 minutes. The cationic starch groups are adsorbed on the surface of fibers and calcium carbonate particles through electrostatic interaction. On the one hand, this strengthens the hydrogen bonding force between fibers, improves the dry strength and folding endurance of the paper, and on the other hand, it increases the retention rate of inorganic fillers, significantly reduces the loss of calcium carbonate with white water, and stabilizes the uniformity of opaque area coverage.
[0073] Step 3: Add alkyl ketene dimer sizing agent Subsequently, the alkyl ketene dimer sizing agent is slowly added and stirred for 8 minutes to promote the esterification and adsorption of the lactone ring of the alkyl ketene dimer sizing agent with the hydroxyl groups of the fiber, forming a continuous hydrophobic protective film on the fiber surface. This gives the paper excellent water resistance, moisture resistance, and resistance to cigarette adhesive penetration. It will not absorb water and wrinkle or lose its light-blocking ability after contact with saliva or moisture in a wet state.
[0074] Step 4: Add polyamide epichlorohydrin wet strength agent Continue adding polyamide epichlorohydrin wet strength agent and stir for 5 minutes. The active groups of polyamide epichlorohydrin wet strength agent nitrogen heterocyclic butyl quaternary ammonium covalently crosslink with the carboxyl groups on the fiber surface. The molecules simultaneously self-crosslink to build a stable water-resistant three-dimensional network, which significantly improves the wet tensile strength of the paper. The paper is not easy to soften or break during cigarette bonding and long-term smoking and soaking.
[0075] Step 5: Add amphoteric polyacrylamide retention aid Finally, the diluted amphoteric polyacrylamide retention aid is added slowly by spraying and stirred for 2-3 minutes. The fine fibers and calcium carbonate microparticles are captured by the dual effects of charge neutralization and polymer bridging, which further improves the overall retention rate of the material, improves the dewatering performance of the pulp, and completes the stable retention and filtration aid system. Short-time stirring can avoid the high shear damage to the filler and fiber flocculation structure formed in the early stage, and ensure the uniformity of paper formation.
[0076] Furthermore, under continuous stirring at a speed of 800–1000 rpm, deionized water was added in portions to dilute the uniformly mixed slurry, with the slurry concentration monitored online in real time to precisely control it to the target online concentration of 1.2%. After dilution, the slurry was sealed and allowed to stand for 30 minutes to eliminate internal micro-stress before use. It should be noted that all fiber disintegration, additive dissolution, and slurry dilution in this application were prepared using deionized water; the conductivity of the deionized water at 25℃ was ≤10 μS / cm, the total hardness (calculated as calcium carbonate CaCO3) was ≤5 mg / L, and the resistivity was ≥0.1 MΩ. cm, free of heavy metal ions such as iron and manganese, will not disrupt the colloidal balance inside the slurry or the dispersion stability of the filler.
[0077] The stirring speed of 900 rpm balances material dispersion efficiency with fiber structure protection, enabling rapid mixing of fillers and various additives without excessive shearing that could damage fibers or generate irregular large flocs. After all fillers and additives have undergone segmented maturation, they are diluted to a specific on-board concentration of 1.2% and allowed to stand in a sealed environment to fully expel micro-air bubbles and balance the system's charge. During on-board forming, fiber and calcium carbonate deposition is uniform, resulting in consistent whiteness and opacity across the entire sheet without localized color differences or translucent spots. The entire process has clearly defined parameters and can be completed using conventional papermaking wet-end equipment. The operation is simple and controllable, with minimal fluctuations in various finished product indicators, and high repeatability for large-scale continuous production. This application utilizes a fully sealed stirring operation, preventing the introduction of large amounts of air during stirring and thus avoiding foaming, thereby maintaining stable pulp concentration and dispersion.
[0078] In some embodiments, the transparent thermochromic zone pulp and the opaque zone pulp are simultaneously fed into the web through a partitioned dual-channel headbox, alternately arranged in fixed-width units, and dewatered under gradient negative pressure. The fibers of the two zones naturally interweave to form an integrated wet paper blank. The headbox distributes the slurry horizontally across the entire width, with each 32mm section forming an independent molding unit. Each molding unit contains a dual-channel structure: an 8mm wide transparent thermochromic slurry channel and a 24mm wide opaque slurry channel. The transparent thermochromic slurry channel is designated as Channel A, and the opaque slurry channel as Channel B. The two channels are evenly distributed horizontally in an alternating A / B pattern. A thin-walled flow-stabilizing weir is installed between each slurry channel, with a 0.3mm fiber weaving gap at the bottom. This prevents lateral flow of slurries with different filtration rates while allowing a small amount of fiber to interweave across the two zones, achieving integrated integration. The transparent thermochromic slurry channel and the opaque slurry channel are each equipped with an independent pressure-stabilizing buffer chamber, allowing for differentiated control of the two slurry flow rates to match the differences in filtration rates between the two types of slurries. During the wet paper blank forming process, the pulp supply pressure is maintained at 0.12-0.15MPa. A single pressure-stabilized pulp supply system is used for the entire width. The paper machine speed is constant at 50m / min. The uniform opening of the headbox lip is 1.1-1.3mm. The dual-channel lips within the unit are proportionally distributed. By using a vacuum chamber with progressively lower negative pressures of -10kPa, -20kPa, and -30kPa, the pulp fibers in the two zones interweave and are integrated into a single unit, resulting in an integrated wet paper blank with a dryness of 32% ± 1%. A 120-mesh polyester forming mesh is laid on the surface of the vacuum chamber to reduce the mesh pore size and further prevent the micron-sized thermochromic microcapsules from being extracted with the white water, ensuring that the microcapsules remain highly within the paper base.
[0079] In a preferred embodiment of this application, the headbox adopts a transverse, full-width, zoned pulp distribution structure, with each forming unit measuring 32mm. Each forming unit is equipped with two channels: an 8mm wide transparent thermochromic zone pulp channel and a 24mm wide opaque zone pulp channel. The pulp concentration in the transparent thermochromic zone is 0.9%, and the pulp concentration in the opaque zone is 1.2%. The two channels are evenly distributed transversely in an alternating A / B pattern. Multiple complete forming units can be formed simultaneously from a single paper web, and subsequent simple cutting yields multiple finished cigarette tipping sheets, effectively improving single-machine production efficiency. The entire system uses a single pressure-stabilized pulp supply system, maintaining a constant pulp pressure of 0.12–0.15 MPa and a fixed paper machine speed of 50 m / min. The headbox lip opening is uniformly 1.1–1.3 mm, and the pulp is distributed proportionally through dual channels within each unit. This ensures equal pulp flow in each forming unit, resulting in straight and regular boundaries between the two zones after forming. The overall paper web exhibits uniform basis weight, light transmission, and opacity, with no localized thickness variations. Alternatively, one transparent thermochromic pulp channel and two opaque pulp channels can be configured, using a three-channel headbox for simultaneous online feeding. The pulp is formed by alternating between the opaque pulp channel, transparent thermochromic pulp channel, and opaque pulp channel, producing a complete paper web that can be cut into multiple finished cigarette tipping sheets.
[0080] Furthermore, a 0.9% transparent thermochromic pulp and a 1.2% opaque pulp are simultaneously sprayed onto the web at the lip. The two pulps intermingle at the unit interface, with fibers interlacing and entangled to directly form a continuous, complete 1020mm wide integrated wet paper blank. This process eliminates the need for secondary lamination processes such as adhesives and hot-pressing, completely avoiding the problems of adhesive aging, moisture penetration leading to interlayer peeling, and paper edge curling inherent in traditional lamination and gluing processes. The two differentiated pulp concentrations are precisely matched to the performance requirements of each zone: the low-concentration pulp is suitable for the low basis weight and high light transmittance of the transparent thermochromic zone, while the high-concentration pulp meets the high filler and high opacity requirements of the opaque zone. Simultaneously, the dewatering rates of the two types of pulp are similar, preventing pulp cross-contamination and fiber orientation shift due to excessive concentration differences. After forming, the boundary between the transparent and opaque zones is clear and the transition is natural.
[0081] Furthermore, a three-stage vacuum gradient dewatering process is employed: -10kPa, -20kPa, and -30kPa, with the dewatering intensity gradually increasing from weak to strong. The initial -10kPa low-pressure stage slowly removes free moisture, allowing sufficient time for the fibers to fully intertwine and entangle, preventing the extraction of fine functional materials such as carboxylated cellulose nanofibers and food-grade water-based acrylic resin from the transparent thermochromic zone by sudden strong suction, thus ensuring that the functional components remain fully within the paper base. The middle stage, at -20kPa, moderately accelerates dewatering, steadily increasing the dryness of the wet paper blank. The final stage, at -30kPa, deeply dewaters, precisely and stably controlling the dryness of the wet paper blank exiting the wire at 32%±1%. This staged dewatering allows the fibers in the two zones to tightly bond under a gentle moisture gradient, resulting in a dense overall structure and moderate initial strength in the wet paper blank, laying an excellent material foundation for subsequent boot press and three-stage gradient drying processes.
[0082] In some embodiments, the process of dewatering the wet paper blank using a ambient temperature boot press and controlling the paper moisture content using a three-stage gradient drying process with progressively decreasing temperature includes: The formed wet paper blank is pressed at room temperature using a shoe press. The pressing environment temperature is 22-28℃, the pressing line pressure is 200kN / m, and the effective pressing zone width is 250mm. A three-stage, progressively cooling, gradient drying process is used to dehydrate the pressed paper: the first stage is a shaping drying at 100℃, with a paper throughput of 8–10 seconds; the second stage is a uniform dehydration drying at 90℃, with a paper throughput of 12–15 seconds; and the third stage is a moisture balance drying at 80℃, with a paper throughput of 10–12 seconds. The finished product moisture content is controlled at 6.0 ± 0.5%.
[0083] In the preferred embodiment of this application, a boot press with a linear pressure of 200 kN / m and an effective longitudinal pressing zone width of 250 mm along the paper feed direction is used. The entire pressing process is carried out at room temperature of 22–28°C without an external heating source. Specifically, the effective longitudinal pressing zone width of the boot is 250 mm, and the effective transverse pressure bearing width is 1020 mm, precisely matching the 1020 mm width of the wet paper blank. This ensures uniform pressure distribution across the entire transverse width of the paper, eliminating defects such as uneven pressure, wrinkles, or insufficient edge dehydration. Unlike traditional high-temperature, high-pressure, instantaneous extrusion processes using hard rollers, this process employs a room-temperature, wide-pressing-zone, low-pressure, gradual-pressing mode. This extends the paper's residence time in the pressing zone, and under gentle mechanical action, steadily increases the wire section dryness from 32% ± 1% to 42%, significantly reducing the heat load and thermal shock intensity of subsequent gradient drying. This ambient temperature, low pressure, and wide-zone pressing method can achieve efficient dehydration without damaging the shell structure of the dual-temperature zone reversible thermochromic microcapsule powder or the fiber network and resin coating system of the transparent thermochromic zone. It eliminates problems such as microcapsule wall material rupture, core material leakage, and premature functional failure caused by high-pressure instantaneous extrusion, and stably preserves the reversible color-changing properties of the dual-temperature zone reversible thermochromic microcapsule powder.
[0084] Furthermore, a three-stage gradient drying process with progressively decreasing temperature is employed to perform segmented temperature-controlled drying of the pressed paper sheet. By dynamically matching the temperature gradient with the paper sheet's moisture content, defects such as microcapsule thermal deactivation, paper warping and deformation, and uneven performance of different zones caused by sudden temperature changes are avoided, ensuring the stability of the temperature-sensitive functional system throughout the process. The first stage is a 100℃ shaping and drying process, with the paper sheet passing through for 8-10 seconds. This stage mainly involves the rapid evaporation of free water on the surface of the paper sheet, quickly locking in the macroscopic structure and zone morphology of the paper sheet, and avoiding paper deformation and boundary shift in the early stages of drying. Under the high moisture content state of the paper sheet, the continuous absorption of heat during water vaporization can buffer the thermal shock brought by the high temperature of the drying cylinder, ensuring that the actual temperature of the paper base is always below the thermal damage threshold of the microcapsules, and preventing premature phase change failure of the microcapsules. The second stage involves uniform dehydration and drying at 90℃, with the paper passing through for 12–15 seconds. This process removes interfiber bound water at a relatively mild temperature, ensuring simultaneous and uniform removal of moisture from both the inside and outside of the paper. This avoids localized over-drying that can cause internal stress, guaranteeing a consistent wet-dry state across the entire paper sheet and maintaining structural stability in both transparent and opaque areas. The third stage is moisture balancing drying at 80℃, with the paper passing through for 10–12 seconds. This process slowly removes residual trace amounts of moisture from the paper, balancing the overall moisture content of the paper base, eliminating drying stress, and stabilizing the dimensional accuracy of the finished product. Through this three-stage gradient cooling drying process, precisely matching the paper's dehydration characteristics, the final moisture content of the finished product is strictly controlled at 6.0 ± 0.5%, ensuring the product's transparency, temperature response accuracy, and long-term dimensional stability.
[0085] In some embodiments, the process of soft calendering of the transparent thermochromic areas of the paper sheet and calendering-free treatment of the opaque areas, followed by low-tension slitting and rewinding to obtain the finished product, includes: The operation of the calendering roller is controlled by a servo partitioned hydraulic pressure control structure. The 8mm transparent temperature change zone in each forming unit is softly calendered. The linear pressure of the calendering roller is 70N / mm and the roller body temperature is 45℃. The 24mm opaque zone is exempt from calendering treatment. After calendering, the paper is treated with transverse segmented hot air leveling and stretching rollers to eliminate the transverse stress difference in the paper web caused by the differentiated calendering of different zones, and to avoid uneven transverse thickness and warping of the finished product. The paper is slit and rewound with low tension of 8-12N, and the waste edges on both sides of the paper are removed to finally produce a finished cigarette tipping paper with zoned transparency and temperature-sensitive turbidity.
[0086] In the preferred embodiment of this application, the calendering roller has a total transverse length of 1020mm and is equipped with a servo-controlled hydraulic pressure control structure. For the 8mm transparent thermochromic zone within each 32mm forming unit, soft calendering is performed using a linear pressure of 70N / mm and a roller temperature of 45℃. The 24mm opaque zone is not calendered. The low-temperature soft calendering of the transparent thermochromic zone smooths the microscopic protrusions on the paper surface, improving the paper surface smoothness to over 500s, reducing diffuse light reflection, and further improving the light transmittance at room temperature. Appropriate compaction of the fiber gaps ensures uniform paper density, providing a uniform and stable carrier for the dual-temperature zone reversible thermochromic microcapsule powder. This results in uniform color development and higher contrast during heat-induced color change. The 45℃ roller temperature is an instantaneous surface contact temperature; the effective contact time between the paper and the roller is less than 1s, and the actual internal temperature of the paper base does not rise to the melting point of the microcapsules, thus preventing premature color development. The opaque areas, designed for calendering-free operation, fully preserve the light-scattering structure of the fiber pores and ultrafine heavy calcium carbonate filler, avoiding the reduction in light-blocking and opacity caused by compaction of the pores. This maintains suitable surface roughness, making it suitable for printing and hot stamping processes. The servo-controlled zoned hydraulic structure allows for independent lateral pressure adjustment of each zone, ensuring that the surface treatment of the transparent temperature-sensitive and opaque areas does not interfere with each other. This allows for the simultaneous achievement of high light transmittance for visualization and high opacity for printing on the same paper.
[0087] Furthermore, the base paper width is 1020mm, with 31 sets of 32mm standard forming units arranged horizontally. A 14mm processing waste edge is reserved on each side of the paper width. The waste edge is removed simultaneously during the slitting process to obtain a standard-sized finished product. The rewinding process is controlled at a low tension of 8-12N throughout, far lower than the high-tension winding range of traditional tipping paper. This low-tension condition avoids paper web stretching deformation and damage to the fiber interweaving structure, preventing stress whitening and micro-crack defects in the transparent thermochromic zone. The finished product has precise zoning dimensions and an intact internal structure. The low-tension base paper feeds smoothly on high-speed cigarette rolling equipment, reducing the likelihood of paper breaks or deviations. Mass production results in consistent physical and chemical properties and appearance of the finished product, significantly improving product yield and batch consistency. It should be noted that the base paper width is 1020mm, with a 14mm processing waste edge reserved on each side, resulting in an effective forming width of 992mm. The headbox is arranged in alternating AB groups of 32mm, with each group containing an 8mm transparent thermochromic zone and a 24mm opaque zone. The finished product is cut with 12mm opaque areas on both sides and 8mm transparent temperature-sensitive area in the middle, with a total width of 32mm for a single finished product. After deducting the areas at the beginning and end that cannot be fully formed (totaling 32mm), 30 qualified cigarette tipping papers can be cut.
[0088] Because the effective width starts at the leftmost end with an 8mm transparent temperature-sensitive zone, and there is no front opaque area for cutting the side, it is impossible to produce the first qualified finished product; the whole width has a total of 31 groups of AB units, and after deducting the first group of units that cannot be fully formed, 30 qualified cigarette tipping papers can be cut in the end.
[0089] The thermochromic cigarette tipping paper in this application adopts an integrated process of fiber pretreatment, zoned flow forming, boot press, gradient drying, zoned soft calendering, and slitting and rewinding. The pulp in the transparent thermochromic zone and the opaque zone are simultaneously fed onto the wire, the fibers are naturally interwoven, and the paper is formed in one go. The entire process does not require additional processing steps such as lamination, gluing, and secondary coating. The process is stable and controllable and suitable for continuous large-scale industrial production.
[0090] The thermochromic cigarette tipping paper obtained using the components and preparation method of the preferred embodiment of this application has a room temperature light transmittance of ≥85% in its transparent thermochromic zone. Through the tipping paper, the internal filter material arrangement and the integrity of the flavor capsules can be directly observed. During cigarette smoking, the transparent thermochromic zone undergoes two-stage reversible color changes as the filter is heated. The color-changing area reflects the heating zone of the filter and the range of smoke action in real time, providing direct feedback on the filter's working status and enhancing the differentiated user experience. This dual-temperature-stage reversible color-changing effect is achieved synergistically by the paper base's internal fibers, functional additives, and molding process, distinguishing it from surface-coated color-changing products, making it difficult to imitate and possessing excellent anti-counterfeiting properties. The dual-temperature-zone reversible thermochromic microcapsule powder is externally coated with melamine-formaldehyde resin and then completely encapsulated with food-grade water-based acrylic resin, effectively preventing the migration and precipitation of internal veil dyes, bisphenol S color developer, and long-chain phase change solvents. All raw and auxiliary materials meet the relevant safety standards for tobacco additives and food contact, ensuring high safety in use. The entire product is constructed using a plant fiber system, without the addition of petrochemical plastics such as polyethylene and polypropylene. It is biodegradable after disposal, making it environmentally friendly. It employs a dual-channel, zoned pulp synchronous online forming process in a single wet process. The transparent and opaque zones interweave fibers, creating a seamless, non-adhesive layer and no composite interface. This prevents delamination and warping, resulting in stable wet and dry strength. It is compatible with high-speed cigarette rolling equipment, minimizing paper breakage. A servo-controlled, zoned hydraulic soft calendering process applies pressure only to the transparent, temperature-sensitive zones to improve light transmission. The opaque zones retain the scattering pores and suitable surface roughness of the ultrafine heavy calcium carbonate filler, providing excellent light-blocking and allowing for smooth processing of printing, hot stamping, die-cutting, and other advanced steps. Continuous mass production requires only minor modifications to existing papermaking equipment. The wood pulp, fillers, and various additives used are all common, readily available materials in the papermaking industry. The finished product exhibits minimal fluctuations in physicochemical properties such as air permeability, wet tensile strength, and smoothness, ensuring controllable overall costs for large-scale production. This invention avoids premature color change defects by using carboxylated cellulose nanofibers and dual-temperature zone reversible thermochromic microcapsule powder with appropriate particle size screening and gradient temperature control production process. It relies on the color difference of two-stage color change and the surface invisible anti-counterfeiting printing to form a double-layer anti-counterfeiting barrier. With multi-color and multi-trigger temperature microcapsule formulations, it can be adapted to the production needs of all types of cigarettes. At the same time, it uses the temperature change color difference to enable cigarette factories to quickly screen for broken capsules and defective filter tip forming products online, which greatly expands the application scenarios of the product.
[0091] The core performance indicators of the cigarette tipping paper in this application are as follows: initial light transmittance at room temperature in the transparent temperature-sensitive zone ≥85%, low-temperature color change trigger temperature 45±1℃, high-temperature color change trigger temperature 60±1℃, rapid recovery to transparent state after temperature drop, color change response time <1.5s, and excellent stability under repeated color change cycles; wet tensile strength ≥9.0kN / m, finished thickness 75±5μm, full-width zone thickness deviation ≤3μm, air permeability 31±2.5CU, coefficient of variation ≤6.0%, curl rate ≤1.0%, and all physical and chemical indicators meet the relevant national standards for cigarette tipping paper.
[0092] To further enhance the anti-counterfeiting level and enrich the functional attributes of the product, a low-temperature flexible printing anti-counterfeiting process is added to the transparent thermochromic area before the finished product leaves the factory. Under normal temperature conditions, water-based food-grade invisible fluorescent anti-counterfeiting ink is printed on the surface of the transparent thermochromic area. The printing ink adheres only to the paper surface in a thin layer and will not penetrate and block the micropores of the fibers, completely preserving the original light transmittance and reversible temperature response characteristics of the paper base. It has no negative impact on the optical properties or temperature-changing function of the substrate. When the cigarette tipping paper is heated to 45°C for light color change and 60°C for dark color change, the invisible anti-counterfeiting graphics on the surface are clearly displayed simultaneously with the temperature-changing color of the paper base. This achieves a dual anti-counterfeiting effect of reversible temperature color change and fluorescent invisible graphics. Relying on the modified internal temperature-changing function of the substrate and the flexible printing composite anti-counterfeiting system on the surface, the product's counterfeiting threshold and traceability are significantly improved. Among them, the entire low-temperature printing process strictly controls the temperature during production, with the printing temperature ≤40℃ and the ink drying temperature <45℃. The entire process is lower than the thermal trigger temperature of the microcapsules and the tolerance temperature of the functional components, so as not to damage the core functional components such as the dual-temperature zone reversible thermochromic microcapsule powder and resin coating structure inside the paper base, ensuring the temperature change accuracy and stability of the finished product.
[0093] In this embodiment, the finished cigarette tipping paper has a total width of 32mm, with an 8mm transparent temperature-changing zone in the middle and 12mm wide opaque zones on each side. The 8mm reversible temperature-changing observation zone is long enough to simultaneously identify local abnormal high temperatures (burst bead breakage points) and the color difference of the overall filter tip during two-stage temperature rise. Its overall size is consistent with the tipping paper dimensions for standard thick-sized cigarettes. Of course, based on this embodiment, different sizes of cigarette tipping paper can also be used according to different cigarette sizes. For example, the finished tipping paper for medium-sized cigarettes has a total width of 28mm, with a 10mm transparent temperature-changing zone in the middle and 9mm opaque zones on each side. After forming, the paper's zoning boundaries are neat and clear, without any overlap. The mismixing of colors effectively increases the visible area of the transparent functional area, resulting in better visualization of the filter's interior. The finished tipping paper for slim cigarettes has a total width of 24mm, with a 7mm transparent temperature-sensitive zone in the middle and 8.5mm opaque zones on both sides. This tipping paper is suitable for 6mm slim filter rods. The finished tipping paper for extra-thick cigarettes has a total width of 36mm, with a 12mm transparent temperature-sensitive zone in the middle and 12mm opaque zones on both sides. This tipping paper is suitable for thicker cigarettes with added flavor capsules. The tipping papers for the aforementioned different cigarette sizes can all use the same formulation components as those in the embodiments of this application, differing only in the width of the transparent and opaque zones during the manufacturing process. It should be noted that the finished width of the tipping paper in this application corresponds to the length along the axial direction of the finished cigarette.
[0094] The technical solution of this invention will be further described in detail and completely below with reference to the gradient variable experiments of key component weight parts. It should be noted that, in the gradient variable experiments, apart from the variables, all other formulation components and preparation processes are the same.
[0095] Experiment 1: Gradient Experiment of Proportioning Fully Bleached Softwood Pulp and Carboxylated Cellulose Nanofibers The baseline ratio (75 parts of fully bleached softwood pulp and 25 parts of carboxylated cellulose nanofibers, i.e., the ratio of the best embodiment of this application) was used to set up 5 groups of variable experimental groups.
[0096]
[0097] Conclusion of Experiment 1: The baseline ratio is the optimal ratio that takes into account light transmission, pulp compatibility, and fixation of functional components; Carboxylated cellulose nanofibers, through filling fiber pores and hydrogen bond anchoring agents, have a significant synergistic effect with fully bleached coniferous long fibers, and are not randomly compounded.
[0098] Experiment 2: Gradient Test of Cationic Transparent Starch Addition The remaining components of the formula remain unchanged, and the cationic transparent starch is set into five groups of variables: 1.0 / 1.5 / 2.0 / 2.5 / 3.0 parts.
[0099] (1) Addition amount <1.5 parts: The fiber coating is incomplete, there are many pores, the loss of fine fillers and carboxylated cellulose nanofibers is too high, the haze of the paper surface increases and the light transmittance decreases; (2) Addition amount = 2.0 parts (basic ratio): The pores are fully filled, the refractive index is optimally matched, and the light transmittance and dryness intensity reach their peak values simultaneously; (3) Addition amount > 2.5 parts: Cationic transparent starch release causes fiber flocculation, excessive pulp viscosity, slow dewatering of the wire section, easy sticking of paper to the cylinder, and brittle paper after drying.
[0100] Experiment 2 Conclusion: 2.0 parts cationic transparent starch is the optimal addition amount for the transparent region, and it synergistically optimizes the transparency performance with carboxylated cellulose nanofibers and sodium carboxymethyl cellulose.
[0101] Experiment 3: Dual-temperature zone reversible thermochromic microcapsule powder The reference material was a dual-temperature zone reversible thermochromic microcapsule powder with a particle size of 2-7 μm and a weight of 0.5 parts. The remaining components of the formulation remained unchanged, and three particle size control groups were set up.
[0102] (1) Particle size < 1 μm: The microcapsule has too large a specific surface area, the slurry adsorbs a large amount of additives, the loss rate of the mesh is 22%, and the color change effect is weak; (2) Particle size 8~12μm: The particles are too large, and the paper is easily broken and leaked when squeezed during papermaking. After 30 days of storage, local pigment migration and contamination of the paper layer will occur. (3) 2~7μm: The capsule has the best stability, with a papermaking breakage rate of <3%, and stable color change performance after 500 cycles.
[0103] Experiment 3 Conclusion: Microcapsules with a particle size of 2~7μm are the optimal choice for wet papermaking systems.
[0104] The technical solution of this invention will be further described in detail and completely below with reference to the key process parameter comparison and verification test. It should be noted that in the comparison and verification test, the formulation components remained unchanged, but the key process parameters in the preparation process were changed. Compared with the benchmark process in this application (paper machine speed 50m / min, three-stage progressively decreasing temperature drying at 100 / 90 / 80℃, shoe press line pressure 200kN / m), the formulation components and other preparation process parameters were the same in the test except for the variable process parameters.
[0105] Experiment 1: Paper machine speed comparison Paper machine speed 60m / min: Insufficient dewatering of pulp, high moisture content of wet paper blank, uneven drying shrinkage, dark spots and uneven light transmission appear in transparent areas; Paper machine speed of 40m / min: Over-drying, increased energy consumption, and decreased thermal stability of functional components. This demonstrates that 50m / min is the optimized speed specifically for this product.
[0106] Experiment 2: Drying Temperature Control 1) The first stage of shaping and drying temperature is raised to 110℃, while the second stage of uniform dehydration and drying temperature and the third stage of moisture balance drying temperature remain unchanged: During shaping and drying, the high temperature impact causes the reversible thermochromic microcapsule powder in the dual temperature zone to easily break, leak, and become discolored and ineffective. 2) The moisture balance drying temperature in the third stage is increased to 90℃, while the shaping drying temperature in the first stage and the uniform dehydration drying temperature in the second stage remain unchanged: the finished product moisture content is <5.0%, the paper loses water and becomes brittle, and the probability of breakage during rolling and splicing is greatly increased.
[0107] Experiment 3: Boot Press Pressure Comparison Pressing pressure 250kN / m: High pressure extrusion damages the outer resin protective film, exposing the functional material and causing it to fail; Pressing pressure 150kN / m: The dryness of the wet paper blank is less than 38%, drying energy consumption surges, and paper surface wrinkles.
[0108] Based on the above, it can be concluded that the paper machine speed of 50m / min, the first stage shaping and drying temperature of 100℃, the third stage moisture balance drying temperature of 80℃, and the shoe press dewatering press line pressure of 200kN / m are all suitable for the cigarette tipping paper forming process parameters of this application.
[0109] The technical solution of this invention will be further described in detail and completely below with reference to comparative examples of the key components in the formulation. It should be noted that, except for the variable components in the comparative examples, the other components, component weights, and preparation processes are the same in different comparative examples.
[0110] Transparent thermochromic zone (parts by weight): 75 parts of fully bleached softwood pulp, 25 parts of carboxylated cellulose nanofibers, 2.0 parts of cationic transparent starch, 0.5 parts of sodium carboxymethyl cellulose, 0.8 parts of sorbitol, 0.5 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.3 parts of food-grade waterborne acrylic resin, 1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.1 parts of amphoteric polyacrylamide retention aid; Opaque area (parts by weight): 90 parts of fully bleached hardwood pulp, 10 parts of fully bleached softwood pulp, 20 parts of heavy calcium carbonate, 1.5 parts of cationic starch, 0.2 parts of alkyl ketene dimer sizing agent, 1.0 part of polyamide epichlorohydrin wet strength agent, and 0.1 parts of amphoteric polyacrylamide retention aid.
[0111] The parameters of the finished product corresponding to the benchmark embodiment are as follows: light transmittance of transparent temperature-sensitive zone at room temperature is 88%, opacity of opaque zone is 90%, smoothness of transparent zone is 540s, wet tensile strength is 9.2kN / m, temperature change response time is 1.0s, number of reversible cycles is >500, and air permeability is 32CU.
[0112] Comparative Example 1: Based on the formulation of the benchmark embodiment, the dual-temperature zone reversible thermochromic microcapsule powder in the transparent temperature-changing zone of the formulation components is not coated with melamine-formaldehyde resin, the formulation of the opaque zone remains unchanged, and the remaining components and preparation process are consistent with the benchmark embodiment.
[0113] Comparison results: During storage and smoking, the exposed color-changing functional components of the finished product have no protective structure and are easily migrated and diffused to the paper surface with environmental moisture and oral saliva, causing local smudging and fading. During use, they will contaminate the cigarette filter and the user's lips, and the exposed pigments will fill the micropores of the fibers, greatly increasing the haze value in the transparent area, resulting in a significant deterioration of light transmission performance and a complete loss of high transparency and visualization effect.
[0114] Comparative Example 2: Based on the formulation of the benchmark embodiment, only the carboxylated cellulose nanofibers were removed from the formulation of the transparent thermochromic region, while the formulation of the opaque region remained unchanged. All other components and preparation processes were consistent with the benchmark embodiment.
[0115] Comparison results: After molding, the gaps between paper-based fibers cannot be effectively filled, and there are a large number of cavities inside the fiber network. Air accumulation causes severe light scattering, resulting in a significant increase in haze in the transparent area of the finished product and a sharp drop in light transmittance. The measured light transmittance is less than 60%, making it impossible to clearly distinguish the burst beads, filter fiber arrangement, and molding state inside the filter rod, thus losing the core visualization function.
[0116] Comparative Example 3: Based on the formulation of the benchmark embodiment, only the food-grade waterborne acrylic resin was removed from the formulation of the transparent temperature-sensitive zone, while the formulation of the opaque zone remained unchanged. All other components and preparation processes were kept consistent with the benchmark embodiment.
[0117] Comparative Results: Without the acrylic resin film-forming protective layer, the microcapsules rely solely on a single layer of resin wall material for protection, significantly reducing the stability of the internal functional structure of the paper base. During papermaking, the microcapsules are susceptible to mechanical shearing damage. During storage and aspiration of the finished product, moisture and saliva easily penetrate the microcapsules, causing deactivation of temperature-sensitive components. The finished product exhibits uneven temperature-sensitive color development, poor reversible cycle stability, and is prone to localized permanent turbidity and transmittance reduction after repeated color changes. Simultaneously, the migration resistance of functional components weakens, significantly reducing safety and product durability.
[0118] Comparative Example 4: Based on the formulation of the baseline example, only food-grade sorbitol was removed from the formulation of the transparent temperature-changing zone, while the formulation of the opaque zone remained unchanged. All other components and preparation processes were kept consistent with the baseline example.
[0119] Comparative results: The lack of sorbitol's plasticizing and moisturizing effects caused the paper base to shrink due to water loss, resulting in microcracks, and the microcapsules were locally crushed and ruptured; at the same time, the paper surface smoothness decreased and the color uniformity deteriorated.
[0120] Comparative Example 5: Based on the formulation of the baseline embodiment, the opaque area is replaced with heavy calcium carbonate with D50 > 0.8 μm, the formulation of the transparent temperature-changing area remains unchanged, and the remaining components and preparation process are consistent with the baseline embodiment.
[0121] Comparative results: Large-particle-size fillers have poor filling properties and low light scattering efficiency, resulting in a significant decrease in the light-blocking ability of opaque areas, with opacity far below 90%, and a mismatch in zone functions. Simultaneously, the filler retention rate is low, the paper surface is rough and uneven, and the finished product's strength, smoothness, and adaptability for further printing and processing are all significantly deteriorated.
[0122] In summary, the present invention discloses a thermochromic tipping paper for cigarettes and its preparation method, which relates to the field of cigarette packaging materials technology. The thermochromic tipping paper for cigarettes includes a central transparent thermochromic zone and opaque zones located on both sides of the transparent thermochromic zone. The transparent thermochromic zone comprises the following components in parts by weight: 70-80 parts of fully bleached softwood pulp, 20-30 parts of carboxylated cellulose nanofibers, 1.5-2.5 parts of cationic transparent starch, 0.3-0.8 parts of sodium carboxymethyl cellulose, 0.6-1.0 parts of food-grade sorbitol, 0.3-0.8 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.2-0.4 parts of food-grade waterborne acrylic resin, 0.8-1.5 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid; The opaque region comprises the following components in parts by weight: 80-95 parts of fully bleached hardwood pulp, 5-20 parts of fully bleached softwood pulp, 15-25 parts of heavy calcium carbonate, 1.0-2.0 parts of cationic starch, 0.1-0.3 parts of alkyl ketene dimer sizing agent, 0.8-1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid.
[0123] In this application, the cigarette tipping paper includes a central transparent thermochromic zone and two opaque zones on both sides. At room temperature, consumers can directly view the internal capsules and filter material distribution structure of the filter rod through the central transparent thermochromic zone. During inhalation, the filter tip gradually heats up as smoke enters, triggering the microcapsules in the transparent thermochromic zone to change color, clearly showing the heated area of the filter tip and the range of smoke action, providing clear feedback on the inhalation status. After cooling down, the thermochromic zone quickly returns to its original transparent state, achieving a reversible color-changing effect, enriching the product's visual identification and inhalation status warning functions. At the same time, the two opaque zones on both sides maintain the excellent printability and overall structural support function of traditional cigarette tipping paper, without reducing the strength and stability of the finished packaging due to the transparent thermochromic zone. The cigarette tipping paper of this application uses food-grade additives and all-plant fiber substrate, without adding petrochemical plastic films such as polyethylene and polypropylene, or harmful additives. It has no adhesive composite structure, relying on the interweaving of fibers to form a single piece, with clear and regular partition boundaries, no seams or delamination, and is biodegradable, fully complying with the food contact safety regulations for tobacco auxiliary materials and the industry's green and environmentally friendly requirements.
[0124] It is understood that those skilled in the art can make equivalent substitutions or modifications to the technical solution and inventive concept of the present invention, and all such substitutions or modifications should fall within the protection scope of the appended claims.
Claims
1. A tipping paper for thermochromic cigarettes, characterized in that, The cigarette tipping paper includes a central transparent thermochromic zone and opaque zones located on both sides of the transparent thermochromic zone; The transparent thermochromic zone comprises the following components in parts by weight: 70-80 parts of fully bleached softwood pulp, 20-30 parts of carboxylated cellulose nanofibers, 1.5-2.5 parts of cationic transparent starch, 0.3-0.8 parts of sodium carboxymethyl cellulose, 0.6-1.0 parts of food-grade sorbitol, 0.3-0.8 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.2-0.4 parts of food-grade waterborne acrylic resin, 0.8-1.5 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid; The opaque region comprises the following components in parts by weight: 80-95 parts of fully bleached hardwood pulp, 5-20 parts of fully bleached softwood pulp, 15-25 parts of heavy calcium carbonate, 1.0-2.0 parts of cationic starch, 0.1-0.3 parts of alkyl ketene dimer sizing agent, 0.8-1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.05-0.15 parts of amphoteric polyacrylamide retention aid.
2. The tipping paper for thermochromic cigarettes according to claim 1, characterized in that, The transparent thermochromic zone comprises the following components in parts by weight: 75 parts of fully bleached softwood pulp, 25 parts of carboxylated cellulose nanofibers, 2.0 parts of cationic transparent starch, 0.5 parts of sodium carboxymethyl cellulose, 0.8 parts of food-grade sorbitol, 0.5 parts of dual-temperature zone reversible thermochromic microcapsule powder, 0.3 parts of food-grade waterborne acrylic resin, 1.2 parts of polyamide epichlorohydrin wet strength agent, and 0.1 parts of amphoteric polyacrylamide retention aid.
3. The tipping paper for thermochromic cigarettes according to claim 1, characterized in that, The opaque region comprises the following components in parts by weight: 90 parts of fully bleached hardwood pulp, 10 parts of fully bleached softwood pulp, 20 parts of heavy calcium carbonate, 1.5 parts of cationic starch, 0.2 parts of alkyl ketene dimer sizing agent, 1.0 part of polyamide epichlorohydrin wet strength agent, and 0.1 parts of amphoteric polyacrylamide retention aid; wherein the particle size D50 of the heavy calcium carbonate is ≤0.8μm.
4. The tipping paper for thermochromic cigarettes according to claim 1, characterized in that, The internal core material of the dual-temperature zone reversible thermochromic microcapsule powder includes a leuco dye, bisphenol S color developer and a long-chain phase change solvent. The outer wall of the dual-temperature zone reversible thermochromic microcapsule powder is coated with melamine-formaldehyde resin. The particle size of the dual-temperature zone reversible thermochromic microcapsule powder is 2-7 μm. The food-grade waterborne acrylic resin has a solid content of 40% to 46%, a viscosity of 800 to 1500 mPa·s at 25°C, and a glass transition temperature (Tg) of 10 to 25°C.
5. A method for preparing tipping paper for thermochromic cigarettes as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Prepare transparent thermochromic slurry and opaque slurry separately; Transparent thermochromic pulp and opaque pulp are simultaneously fed into the web through a partitioned dual-channel headbox and arranged alternately in fixed width units. After being dewatered by gradient negative pressure, the fibers of the two zones naturally interweave to form an integrated wet paper blank. The wet paper blank is dehydrated by ambient temperature boot press; A three-stage gradient drying process with progressively decreasing temperature is used to control the moisture content of the paper. The transparent thermochromic areas of the paper are soft-calendered, while the opaque areas are left uncalendered. The paper is then slit and rewound under low tension to obtain the finished product.
6. The method for preparing tipping paper for thermochromic cigarettes according to claim 1, characterized in that, The step of preparing the transparent temperature-sensitive slurry includes: Fully bleached softwood pulp was diluted in deionized water to a disintegration concentration of 3.5%–4.0%. The fibers were then broken down in a pulper until completely dispersed without fiber bundles. Carboxylated cellulose nanofibers were then added and mixed evenly to obtain a transparent thermochromic mixed pulp. The transparent thermochromic mixed pulp was then placed in a high-consistency refiner and refined at an input concentration of 3.8%–4.2%. The pulp freeness was controlled at 92±3°SR and the average fiber length was 0.8–1.0 mm to obtain a transparent thermochromic fiber-based pulp. Under stirring conditions of 800-1000 rpm, cationic transparent starch, sodium carboxymethyl cellulose, food-grade sorbitol, polyamide epichlorohydrin wet strength agent, and amphoteric polyacrylamide retention aid are added sequentially to the transparent thermochromic fiber-based slurry. After each component is added, it is stirred and matured separately to ensure that the additives are fully dispersed and adsorbed, thus forming a transparent slurry modified with additives. The dual-temperature zone reversible thermochromic microcapsule powder and food-grade waterborne acrylic resin were premixed and dispersed evenly at room temperature. After the aforementioned additives had matured in stages, the stirring speed was reduced from 800-1000 rpm to a low-shear stirring state of 500 rpm. Then, the dual-temperature zone reversible thermochromic microcapsule powder and food-grade waterborne acrylic resin functional materials were slowly added into the transparent slurry modified with the additives. After functional modification, the transparent slurry is diluted with deionized water to a concentration of 0.9% for online application. After stirring evenly, it is sealed and allowed to stand for 20-30 minutes to mature.
7. The method for preparing tipping paper for thermochromic cigarettes according to claim 1, characterized in that, The step of preparing the opaque slurry includes: Fully bleached hardwood pulp and fully bleached softwood pulp were mixed and adjusted to a disintegration concentration of 4.0% in deionized water. The pulp was then disintegrated in a pulper until completely dispersed to obtain an opaque mixed pulp. The opaque mixed pulp was then beating with a double-disc refiner to control the beating degree of the pulp at 40±3°SR, thus obtaining an opaque fiber-based pulp. At a stirring speed of 800-1000 rpm, heavy calcium carbonate, cationic starch, alkyl ketone dimer sizing agent, polyamide epichlorohydrin wet strength agent, and amphoteric polyacrylamide retention aid are added sequentially to the opaque fiber-based slurry. After each component is added, it is stirred and matured separately to ensure that the additives are fully dispersed and adsorbed, thus forming an opaque slurry modified with additives. The modified opaque slurry was diluted with deionized water to a concentration of 1.2% for online processing. After stirring evenly, it was sealed and allowed to stand for 20-30 minutes to mature.
8. The method for preparing tipping paper for thermochromic cigarettes according to claim 5, characterized in that, The transparent thermochromic pulp and the opaque pulp are simultaneously fed into the web through a partitioned dual-channel headbox, arranged alternately in fixed-width units, and dewatered under gradient negative pressure. The fibers from the two zones naturally interweave to form an integrated wet paper blank. The slurry is distributed horizontally across the entire width of the headbox, with each 32mm section forming an independent molding unit. Each molding unit is equipped with a dual-channel structure, consisting of an 8mm wide transparent thermochromic slurry channel and a 24mm wide opaque slurry channel. The transparent thermochromic slurry channel is defined as channel A, and the opaque slurry channel is defined as channel B. The dual channels are evenly distributed horizontally in an alternating AB pattern. During the wet paper blank forming process, the pulp supply pressure is maintained at 0.12-0.15MPa. A single pressure-stabilized pulp supply system is used for the entire width. The paper machine speed is constant at 50m / min. The uniform opening of the headbox lip is 1.1-1.3mm. The dual-channel lips within the unit are proportionally distributed. By using a vacuum chamber with progressively lower negative pressures of -10kPa, -20kPa, and -30kPa, the pulp fibers in the two zones interweave and are integrated into a single unit, resulting in an integrated wet paper blank with a dryness of 32% ± 1%.
9. The method for preparing tipping paper for thermochromic cigarettes according to claim 5, characterized in that, The process of dewatering the wet paper blank using a room-temperature boot press and controlling the paper moisture content using a three-stage gradient drying process with progressively decreasing temperature includes: The formed wet paper blank is pressed at room temperature using a shoe press. The pressing environment temperature is 22-28℃, the pressing line pressure is 200kN / m, and the effective pressing zone width is 250mm. A three-stage, progressively cooling, gradient drying process is used to dehydrate the pressed paper: the first stage is a shaping drying at 100℃, with a paper throughput of 8–10 seconds; the second stage is a uniform dehydration drying at 90℃, with a paper throughput of 12–15 seconds; and the third stage is a moisture balance drying at 80℃, with a paper throughput of 10–12 seconds. The finished product moisture content is controlled at 6.0 ± 0.5%.
10. The method for preparing tipping paper for thermochromic cigarettes according to claim 5, characterized in that, The process involves soft calendering of the transparent thermochromic areas of the paper and calendering-free treatment of the opaque areas, followed by low-tension slitting and rewinding to obtain the finished product, which includes: The operation of the calendering roller is controlled by a servo partitioned hydraulic pressure control structure. The 8mm transparent temperature change zone in each forming unit is softly calendered. The linear pressure of the calendering roller is 70N / mm and the roller body temperature is 45℃. The 24mm opaque zone is exempt from calendering treatment. After calendering, the paper is treated with transverse segmented hot air leveling and stretching rollers to eliminate the transverse stress difference in the paper web caused by the differentiated calendering of different zones, and to avoid uneven transverse thickness and warping of the finished product. The paper is slit and rewound with low tension of 8-12N, and the waste edges on both sides of the paper are removed to finally produce a finished cigarette tipping paper with zoned transparency and temperature-sensitive turbidity.